Method for manufacturing electrostatic latent image developing carrier and method for manufacturing electrostatic latent image developer
By adopting the methods of process A, process B and process C in the electrostatic latent image development technology, the problem of difficulty in completely fixing the resin coating layer on the surface of the magnetic particles is solved, and the dimming of the image color is suppressed and the image quality is stabilized. promote.
Patent Information
- Application Number
- CN202410734257.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-19
- Filing Date
- 2024-06-07
- Publication Date
- 2025-01-21
AI Technical Summary
In the existing electrostatic latent image development technology, it is difficult to completely fix the resin coating layer on the surface of magnetic particles, resulting in dull color and unstable quality of the image.
Using a manufacturing method including steps A, B and C, the resin and magnetic particles are heated in a mixer to form a resin coating layer, and the resin-coated magnetic particles are flowed in a fluidized bed device and then cooled to ensure that the resin The stability of the cladding and the excellence of the image color.
Through this method, the occurrence of color dulling in the image is significantly suppressed, and the color dulling suppressing properties of the carrier for developing electrostatic latent images and the stability of the image quality are improved.
Smart Images

Figure CN119335829A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a carrier for electrostatic latent image development and a method for producing an electrostatic latent image developer. Background Art
[0002] Patent document 1 discloses a method for manufacturing a carrier for electrostatic latent image development, which includes a coating process, in which a coating liquid containing a resin and a solvent and magnetic particles are added to a mixer having a stirring blade to form a resin coating layer on the surface of the magnetic particles, and the carrier with the resin coating layer is taken out from the mixer. The stirring conditions in the coating process, from heating in the mixer to evaporate the solvent and drying it until it is taken out from the mixer, meet the conditions of the following formulas 1 and 2.
[0003] 0.2≤the peripheral speed of the stirring blade πDN (m / s)≤2.0 Formula 1
[0004] 1×10 3 ≤Stirring workload (circumferential speed × stirring time T) ≤4×10 3 Formula 2
[0005] In Formula 1 and Formula 2, D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
[0006] Patent Document 2 discloses a method for producing an electrophotographic carrier, wherein an air flow classifier is used to homogenize the carrier in the method for producing an electrophotographic carrier including a carrier core material and a resin covering the surface of the carrier core material.
[0007] Patent Document 1: Japanese Patent Application Publication No. 2022-147738
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 8-234499 Summary of the invention
[0009] The present invention aims to provide a method for producing a carrier for electrostatic latent image development, which comprises steps A, B and C, and the temperature T A When the temperature is lower than the glass transition temperature Tg-20°C and step B is not performed, or the temperature T BIn the step A, a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer, and heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are maintained at a temperature Tg. A In the step B, the resin-coated magnetic particles after the step A are flowed in a fluidized bed device while being maintained at a temperature TB. In the step C, the resin-coated magnetic particles after the step B are cooled.
[0010] Means for solving the above-mentioned problems include the following aspects.
[0011] <1> A method for producing a carrier for developing an electrostatic latent image, comprising:
[0012] Step A, mixing a mixed solution containing a resin having a glass transition temperature Tg and a solvent with magnetic particles in a mixer, and heating the mixture to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then maintaining the resin-coated magnetic particles at a temperature Tg. A Decomposition and crushing in a state;
[0013] Step B, in a fluidized bed apparatus, maintaining the resin-coated magnetic particles after step A at a temperature T B flows in a state of
[0014] Step C, cooling the resin-coated magnetic particles after step B,
[0015] The temperature T A And the temperature T B The glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower are satisfied independently.
[0016] <2> The method for producing a carrier for electrostatic latent image development according to <1>, wherein:
[0017] In the step A, the resin-coated magnetic particles are stirred at a temperature T using a mixer having a stirring blade. A The stirring conditions in the mixer when decomposing and pulverizing are performed in a state satisfy the conditions of the following formula 1 and the following formula 2.
[0018] 0.2≤the peripheral speed of the stirring blade πDN (m / s)≤2.0 Formula 1
[0019] 5×10 2 ≤Stirring workload (circumferential speed πDN×stirring time T)≤1.5×10 3 Formula 2
[0020] In Formula 1 and Formula 2, D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
[0021] <3> The method for producing a carrier for electrostatic latent image development according to <2>, wherein:
[0022] The conditions of the above formula 2 are the conditions of the following formula 2'.
[0023] 7×10 2 ≤Stirring workload (circumferential speed πDN×stirring time T)≤1×10 3 Formula 2'
[0024] In Formula 2', D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
[0025] <4> The method for producing a carrier for developing an electrostatic latent image according to any one of <1> to <3>, wherein:
[0026] In the step B, the resin-coated magnetic particles after the step A are maintained at a temperature T B In the step C, the temperature T of the resin-coated magnetic particles is lowered to C Cool to the glass transition temperature Tg-40°C or below.
[0027] <5> The method for producing a carrier for electrostatic latent image development according to any one of <1> to <4>, wherein:
[0028] In the step B, the resin-coated magnetic particles after the step A are maintained at a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H (m / s) satisfies 1 to 5 times the minimum fluidization velocity Umf.
[0029] <6> The method for producing a carrier for developing an electrostatic latent image according to <5>, wherein:
[0030] The superficial velocity V of the fluidizing gas in the fluidized bed device H Satisfies a minimum fluidization velocity of at least 2 times and at most 3 times the minimum fluidization velocity Umf.
[0031] <7> A method for producing an electrostatic latent image developer, comprising the method for producing a carrier for electrostatic latent image development according to any one of <1> to <6>.
[0032] Effects of the Invention
[0033] According to the invention described in <1>, there is provided a method for producing a carrier for developing an electrostatic latent image, wherein the method comprises steps A, B and C, and wherein the temperature T A When the temperature is lower than the glass transition temperature Tg-20°C and step B is not performed, or the temperature T B In the step A, a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer, and heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are maintained at a temperature Tg. A In step B, the resin-coated magnetic particles after step A are maintained at a temperature T in a fluidized bed apparatus. B In step C, the resin-coated magnetic particles after step B are cooled.
[0034] According to the invention described in <2>, there is provided a method of maintaining the temperature T of the resin-coated magnetic particles in step A. A A method for producing a carrier for electrostatic latent image development having better color fading suppression of the obtained image when the stirring conditions in the mixer during decomposition and pulverization do not satisfy the conditions of the above-mentioned formula 2.
[0035] According to the invention described in <3>, there is provided a method of maintaining the temperature T of the resin-coated magnetic particles in step A. A A method for producing a carrier for electrostatic latent image development having better color fading suppression of the obtained image when the stirring conditions in the mixer during decomposition and pulverization satisfy the conditions of the above formula 2 but do not satisfy the conditions of the above formula 2'.
[0036] According to the invention described in <4>, there is provided a method of maintaining the resin-coated magnetic particles at a temperature T B After the resin-coated magnetic particles flow for less than 30 minutes, the temperature T C When the resin-coated magnetic particles after step A are cooled to a glass transition temperature Tg-40°C or lower, or when the resin-coated magnetic particles after step A are maintained at a temperature T B After the resin-coated magnetic particles flow for more than 30 minutes, the temperature T C A method for producing a carrier for developing an electrostatic latent image, wherein the carrier is cooled to a temperature lower than the glass transition temperature Tg-40° C., and the obtained image has a more excellent color fading suppression property.
[0037] According to the invention described in <5>, there is provided a method of maintaining the resin-coated magnetic particles after step A at a temperature T in step B. B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H A method for producing a carrier for developing an electrostatic latent image in which the color fading of the obtained image is more excellent when the minimum fluidization velocity (m / s) exceeds 5 times the minimum fluidization velocity Umf.
[0038] According to the invention of <6>, there is provided a method of maintaining the resin-coated magnetic particles after step A at a temperature T in step B. B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H A method for producing a carrier for developing an electrostatic latent image in which the color fading of the obtained image is more excellent when the minimum fluidization velocity Umf (m / s) is more than 3 times and less than 5 times.
[0039] According to the invention described in <7>, there is provided a method for producing an electrostatic latent image developer, which comprises steps A, B and C, and wherein the temperature T A When the temperature is lower than the glass transition temperature Tg-20°C and step B is not performed, or the temperature T B The method for producing a carrier for electrostatic latent image development having a glass transition temperature lower than the glass transition temperature Tg-20°C or higher than the glass transition temperature Tg+50°C has excellent color fading suppression of the obtained image, wherein in the step A, a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer and heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are heated to a temperature of Tg. AIn step B, the resin-coated magnetic particles after step A are maintained at a temperature T in a fluidized bed apparatus. B In step C, the resin-coated magnetic particles after step B are cooled. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Embodiments of the present invention will be described in detail with reference to the following drawings.
[0041] Figure 1 is a schematic structural diagram showing an example of an image forming apparatus according to the present embodiment;
[0042] Figure 2 is a schematic structural diagram showing an example of a process cartridge that is mounted and removed from the image forming apparatus according to the present embodiment;
[0043] Figure 3 This is a schematic graph showing changes in the load power value of the stirring blade and changes in the temperature inside the mixer with the passage of time in an example of the method for producing the electrostatic latent image developing carrier according to the present embodiment.
[0044] Explanation of symbols
[0045] 1Y, 1M, 1C, 1K-photoreceptor (an example of an image holding body), 2Y, 2M, 2C, 2K-charging roller (an example of a charging member), 3-exposure device (an example of an electrostatic latent image forming member), 3Y, 3M, 3C, 3K-laser beam, 4Y, 4M, 4C, 4K-developing device (an example of a developing member), 5Y, 5M, 5C, 5K-primary transfer roller (an example of a primary transfer member), 6Y, 6M, 6C, 6K-photoreceptor cleaning device (an example of a cleaning member), 8Y, 8M, 8C, 8K-toner cartridge, 10Y, 10M, 10C, 10K-image forming unit, 20-intermediate transfer belt (an example of an intermediate transfer body), 22-driving roller, 24-support roller, 26- Secondary transfer roller (an example of a secondary transfer component), 28-fixing device (an example of a fixing component), 30-intermediate transfer body cleaning device, P-recording paper (an example of a recording medium), 107-photosensitive body (an example of an image holding body), 108-charging roller (an example of a charging component), 109-exposure device (an example of an electrostatic latent image forming component), 111-developing device (an example of a developing component), 112-transfer device (an example of a transfer component), 113-photosensitive body cleaning device (an example of a cleaning component), 115-fixing device (an example of a fixing component), 116-mounting guide, 117-frame, 118-opening portion for exposure, 200-processing box, 300-recording paper (an example of a recording medium). DETAILED DESCRIPTION
[0046] Hereinafter, embodiments of the present invention will be described. These descriptions and examples are for illustrating the embodiments and do not limit the scope of the embodiments.
[0047] In the present invention, a numerical range expressed using "to" indicates a range including the numerical values before and after "to" as the minimum value and the maximum value, respectively.
[0048] In the numerical ranges recorded in stages in the present invention, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. And, in the numerical ranges recorded in the present invention, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment.
[0049] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.
[0050] When the embodiments of the present invention are described with reference to the drawings, the structure of the embodiments is not limited to the structure shown in the drawings. In addition, the sizes of the components in the drawings are conceptual, and the relative relationship between the sizes of the components is not limited thereto.
[0051] In the present invention, each component may contain a plurality of corresponding substances. When the amount of each component in the composition is mentioned in the present invention, when there are a plurality of substances corresponding to each component in the composition, unless otherwise specified, it refers to the total amount of the plurality of substances present in the composition.
[0052] In the present invention, multiple types of particles corresponding to each component may be contained. When multiple types of particles corresponding to each component are present in the composition, unless otherwise specified, the particle size of each component represents a value for a mixture of the multiple types of particles present in the composition.
[0053] In the present invention, “(meth)acrylic acid” means at least one of acrylic acid and methacrylic acid, and “(meth)acrylate” means at least one of acrylate and methacrylate.
[0054] In the present invention, carbon black is not included in the inorganic particles.
[0055] In the present invention, “toner for electrostatic latent image development” is also referred to as “toner”, “carrier for electrostatic latent image development” is also referred to as “carrier”, and “electrostatic latent image developer” is also referred to as “developer”.
[0056] <<Method for producing carrier for electrostatic latent image development>>
[0057] The method for producing a carrier for electrostatic latent image development according to the present embodiment is a method for producing a carrier for electrostatic latent image development, comprising: step A, mixing a mixed solution containing a resin having a glass transition temperature Tg and a solvent with magnetic particles in a mixer, and heating the mixture to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then heating the resin-coated magnetic particles at a temperature maintained at Tg. A Step B, in a fluidized bed apparatus, the resin-coated magnetic particles after step A are maintained at a temperature T B and step C, the resin coated magnetic particles after step B are cooled, the temperature T A And the temperature T B The glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower are satisfied independently.
[0058] In the manufacture of a carrier using a dip coating method, the following steps are included: a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer, and heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are decomposed and crushed. When obtaining the resin-coated magnetic particles, the solvent is evaporated by heating, so that the resin-coated magnetic particles become a temperature close to the glass transition temperature Tg of the resin. Therefore, if the obtained resin-coated magnetic particles are decomposed and crushed while being cooled, the resin coating layer that is not completely fixed to the magnetic particles is easily peeled off due to the shear force applied to the resin-coated magnetic particles. The coating residue components such as resin flakes generated by the peeled resin coating layer are developed together with the toner, and in particular, in yellow toners or transparent toners, etc., the color is sometimes dull due to the coating residue components. Due to the further improvement of quality requirements, it is expected to further reduce the coating residue components to suppress the occurrence of dull color of the obtained image.
[0059] In the method for producing a carrier for electrostatic latent image development according to the present embodiment, when the resin-coated magnetic particles having the resin coating layer formed on the surface of the magnetic particles are decomposed and crushed, the resin-coated magnetic particles are set to a temperature T A When the decomposed and crushed resin-coated magnetic particles are made to flow, the resin-coated magnetic particles are set to a temperature T B Then, the resin-coated magnetic particles are cooled. Then, the temperature T A and temperature T BThe glass transition temperature Tg of the resin contained in the resin coating layer (or the resin contained in the mixed solution) is independently set to be above Tg-20°C and below Tg+50°C. It is speculated that the resin-coated magnetic particles are decomposed and crushed while maintaining such a temperature range (uncooled state), and the decomposed and crushed resin-coated magnetic particles are made to flow, and then the resin-coated magnetic particles are cooled, thereby promoting the fixation of the resin coating layer on the magnetic particles and then cooling the resin-coated magnetic particles, thereby reducing the peeling of the resin coating layer. As a result, in the method for manufacturing a carrier for electrostatic latent image development involved in this embodiment, the color dullness caused by the coating residue component in the obtained image can be suppressed.
[0060] Hereinafter, each step in the method for producing the electrostatic latent image developing carrier according to the present embodiment will be described in detail.
[0061] <Process A>
[0062] The method for producing a carrier for electrostatic latent image development according to the present embodiment includes step A, wherein a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer, and then heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are heated at a temperature maintained at Tg. A Decomposition and crushing are carried out in a state.
[0063] Here, the temperature T A The glass transition temperature is greater than Tg-20°C and less than Tg+50°C.
[0064] Hereinafter, when referring to the "glass transition temperature Tg", it means the glass transition temperature Tg of the resin contained in the mixed liquid (resin contained in the resin coating layer).
[0065] Furthermore, a “mixed liquid containing a resin having a glass transition temperature Tg and a solvent” is also simply referred to as a “mixed liquid”.
[0066] That is, in step A, when the resin-coated magnetic particles formed by forming the resin coating layer on the surface of the magnetic particles are decomposed and crushed, the temperature of the resin-coated magnetic particles is maintained at a temperature Tg in the range of not less than Tg-20°C and not more than Tg+50°C based on the glass transition temperature Tg of the resin contained in the mixed solution (resin contained in the resin coating layer). A is carried out in the state of.
[0067] For example, if the glass transition temperature Tg of the resin is 110°C, then the temperature T AThe temperature may be 90°C or higher and 160°C or lower.
[0068] In the present embodiment, when the mixed liquid contains two or more resins (when the resin coating layer contains two or more resins), the glass transition temperature Tg of the resin is set to the Tg of the resin with the lower glass transition temperature among the two or more resins.
[0069] Furthermore, in order to maintain the resin-coated magnetic particles at a temperature T A , just adjust the main body temperature of the mixer to become temperature T A That's it.
[0070] Temperature T A The determination was as follows.
[0071] That is, for temperature T A A thermometer is set at a location in the mixer that can contact the resin-coated magnetic particles to measure the temperature, or a thermometer is set at a location that does not contact the resin-coated magnetic particles to measure the atmosphere temperature in the mixer.
[0072] From the viewpoint of further improving the color fading suppression of the obtained image, the temperature T A For example, it is preferable to satisfy the glass transition temperature of Tg-20°C or higher and the glass transition temperature of Tg+20°C or lower, and it is more preferable to satisfy the glass transition temperature of Tg-15°C or higher and the glass transition temperature of Tg or lower. This is because in step A, if the stirring workload is excessively applied at a temperature from the glass transition temperature of Tg to 50°C or higher, the resin coating layer formed on the surface of the magnetic particles will be peeled off, so it is preferably near Tg, for example.
[0073] From the viewpoint of further improving the color fading suppression of the obtained image, for example, when the resin-coated magnetic particles are decomposed and crushed, it is preferable to perform the crushing with a weak shear force. Specifically, in step A, for example, a mixer having a stirring blade is used to mix the resin-coated magnetic particles at a temperature maintained at T A The stirring conditions in the mixer when performing decomposition and pulverization in a state preferably satisfy the conditions of the following formula 1 and the following formula 2.
[0074] 0.2≤Circumferential speed of stirring bladeπDN(m / s)≤2.0 Formula 1
[0075] 5×10 2 ≤Mixing workload (circumferential speed πDN×mixing time T)≤1.5×10 3 Formula 2
[0076] In Formula 1 and Formula 2, D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
[0077] In addition, π represents the ratio of a circle to a circumference of ...
[0078] It is considered that in step A, for example, Figure 3 The change in load power value of the stirring blade is shown.
[0079] Figure 3 This is a schematic graph showing changes in the load power value of the stirring blade and changes in the temperature inside the mixer with the passage of time in an example of the method for producing the electrostatic latent image developing carrier according to the present embodiment.
[0080] Figure 3 The vertical axis on the left side represents the load power value (kW) of the stirring blade, the vertical axis on the right side represents the temperature in the mixer (°C), and the horizontal axis represents the elapsed time (min).
[0081] exist Figure 3 At T0 shown in FIG. 1 , a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are put into a mixer, and the mixed solution and magnetic particles are mixed from T0 to T1. Figure 3 In the process, from T1 to T2, heating is performed and, if necessary, decompression is performed while evaporating the solvent contained in the mixed solution, a resin coating layer is formed on the surface of the magnetic particles to obtain resin-coated magnetic particles, until the drying of the resin-coated magnetic particles is completed, and from T2 to T3, the dried resin-coated magnetic particles are decomposed and crushed. In addition, in T3, the stirring in the mixer is completed, and the carrier is taken out from the mixer.
[0082] about Figure 3 The change in the load power value of the stirring blade is shown as follows.
[0083] From T0 to T1, the load power value of the stirring blade is approximately constant.
[0084] From T1 to T2, as the solvent evaporates, the viscosity of the mixture of the mixed liquid and the magnetic particles in the mixer increases, and the load power value of the stirring blade continues to rise until the drying of the resin-coated magnetic particles is completed. If the drying of the resin-coated magnetic particles is completed, the load power value of the stirring blade decreases sharply to a value less than 1.3 times the load power value of the stirring blade from T0 to T1.
[0085] From T2 to T3, the load power value of the stirring blade is approximately constant again.
[0086] The T becomes the time from T2 to T3.
[0087] And, about Figure 3 The temperature fluctuations in the mixer are shown below.
[0088] From T0 to T1, the temperature is gradually increased to the set temperature (for example, jacket temperature).
[0089] From T1 to T2, the temperature does not rise steadily due to the heat of vaporization of the solvent. However, overall, the temperature gradually rises as the drying of the resin-coated magnetic particles proceeds.
[0090] From T2 to T3, the set temperature (for example, the jacket temperature) is controlled so that the temperature of the resin-coated magnetic particles becomes the temperature T A within the range.
[0091] The mixer used in the step A may be any mixer having a stirring blade, and a known mixer may be used. However, from the viewpoint of drying properties, for example, a vacuum mixer is preferred.
[0092] Furthermore, from the viewpoint of miscibility and color fading suppression of the obtained image, the mixer used in the step A is preferably, for example, a batch mixer, and more preferably a batch vacuum mixer.
[0093] Moreover, as a batch mixer, for example, a blade type kneading machine is preferred, and the direction of the rotation axis of the scraper may be vertical or horizontal. Among the vertical types, there are spiral mixers (manufactured by AICOHSHA MFG.CO., LTD.) and planetary mixers (manufactured by INOUE MFG., INC.), and among the horizontal types, there are kneaders (manufactured by INOUE MFG., INC.). Among them, from the viewpoint of mixing properties and color fading suppression of the obtained image, for example, a twin-screw horizontal kneader is particularly preferred.
[0094] Furthermore, the mixer preferably has, for example, a temperature control structure capable of heating and cooling under reduced pressure in the mixing tank, and a mechanism capable of detecting the stirring power value of the stirring blade.
[0095] The temperature regulating structure is not particularly limited, but a jacket structure is preferred.
[0096] The shape of the stirring blade in the mixer is not particularly limited, and examples thereof include Banbury-type, sigma-type, Z-type, spiral-type, and fishtail-type shapes.
[0097] The diameter D of the stirring blade is not particularly limited as long as it is a size corresponding to the mixer used. In addition, the diameter D of the stirring blade in this embodiment is the maximum outer diameter of the portion through which the stirring blade passes when rotating on a plane perpendicular to the rotation axis.
[0098] From the viewpoint of the manufacturing speed of the resin-coated magnetic particles and the color dullness suppression of the obtained image, for example, in the mixer in the embodiment, the rotation speed N of the stirring blade is preferably greater than 10 rpm and less than 200 rpm, more preferably greater than 15 rpm and less than 150 rpm, further preferably greater than 20 rpm and less than 100 rpm, and particularly preferably greater than 40 rpm and less than 60 rpm.
[0099] This is because the gap (interval) between the stirring tank and the stirring blade in the mixer is not particularly limited and becomes a size corresponding to the mixer used. However, if the gap is wide, not only the resin-coated magnetic particles stored at the bottom cannot be completely decomposed and crushed, but also the shear force is determined not only by the peripheral speed of the stirring blade and the stirring workload, but also by the gap. Therefore, the narrower the gap, the better, but due to the limitations of the manufacturing of the device, the gap has a limit, so for the gap between the periphery of the stirring blade and the stirring tank, the value of the gap / diameter of the stirring blade is preferably less than 5%, and more preferably less than 3.5%.
[0100] The time T from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying progresses and the moment when the drying is completed and the load power value decreases to 1.3 times or less of the value before the drying to the moment when the stirring in the mixer is terminated, from the viewpoint of suppressing the color fading of the obtained image, the stirring time T needs to be determined according to the peripheral speed so as to be 5×10 2 ≤Mixing workload (circumferential speed πDN×mixing time T)≤1.5×10 3 : Formula 2. For example, in the mixer in the examples, it is preferably 5 minutes to 100 minutes, more preferably 8 minutes to 80 minutes, further preferably 15 minutes to 60 minutes, and particularly preferably 15 minutes to 45 minutes.
[0101] Furthermore, in step A, stirring is preferably continued using, for example, a stirring blade.
[0102] In step A, a mixer having a stirring blade is used to mix the resin-coated magnetic particles at a temperature T A The stirring conditions in the mixer when performing decomposition and pulverization in a state preferably satisfy the conditions of the following formula 1', and more preferably satisfy the conditions of the following formula 1".
[0103] 0.3≤the circumferential speed of the stirring blade πDN(m / s)≤1.0Formula 1'
[0104] 0.5≤the circumferential speed of the stirring blade πDN(m / s)≤0.8Formula 1”
[0105] In step A, the resin-coated magnetic particles are mixed at a temperature T A The stirring conditions in the mixer when the decomposition and pulverization are performed in a state preferably satisfy the conditions of the following formula 2', for example. That is, the conditions of formula 2 are preferably the conditions of the following formula 2', for example.
[0106] 7×10 2 ≤Mixing workload (circumferential speed πDN×mixing time T)≤1×10 3 Formula 2'
[0107] In step A, the solvent can be evaporated by heating under normal pressure, by reducing pressure, or by heating under reduced pressure. However, since drying does not need to be performed from the boiling point of the solvent to above the glass transition temperature Tg of the resin, it is preferred to evaporate the solvent by heating under reduced pressure, for example.
[0108] The air pressure in the mixer in step A is not particularly limited as long as it is appropriately selected according to the glass transition temperature Tg of the resin and the solvent used. However, from the viewpoint of the evaporation rate of the solvent and the color darkening suppression of the obtained image, it is preferably 0.1 kPa-a or more and 80 kPa-a or less, and more preferably 5 kPa-a or more and 60 kPa-a or less.
[0109] In addition, kPa-a represents the air pressure (kPa) based on the absolute pressure.
[0110] The decompression means in the mixer is not particularly limited, and a known decompression means such as a decompression pump can be used.
[0111] Furthermore, the evaporated solvent can be recovered by a solvent recovery member such as a cooling trap.
[0112] When the decomposition and pulverization of the resin-coated magnetic particles in step A is completed, the resin-coated magnetic particles are taken out of the mixer.
[0113] In addition, the temperature of the resin-coated magnetic particles when taken out of the mixer is maintained at a temperature T A .
[0114] The amounts of the mixed solution and magnetic particles used in step A are not particularly limited and may be appropriately selected depending on the disperser etc. used.
[0115] The quantitative ratio of the mixed solution and the magnetic particles may be appropriately selected according to the concentration of the mixed solution, the thickness of the resin coating layer to be formed, and the like.
[0116] Furthermore, in step A, in addition to the mixed solution and the magnetic particles, other components contained in the resin coating layer of the particles, etc., may be added to the mixer.
[0117] The mixed solution containing the resin and the solvent, the magnetic particles, and other components used in the step A will be described in detail later.
[0118] <Process B>
[0119] The method for producing a carrier for electrostatic latent image development according to the present embodiment includes step B, in which the resin-coated magnetic particles obtained after step A are maintained at a temperature T in a fluidized bed apparatus. B flows in the state of.
[0120] Here, the temperature T B The glass transition temperature is greater than Tg-20°C and less than Tg+50°C.
[0121] That is, in step B, when the resin-coated magnetic particles decomposed and crushed in step A are made to flow, the temperature of the resin-coated magnetic particles is maintained at a temperature Tg in the range of not less than Tg-20°C and not more than Tg+50°C based on the glass transition temperature Tg of the resin contained in the mixed liquid (resin contained in the resin coating layer). B is carried out in the state of.
[0122] For example, if the glass transition temperature Tg of the resin is 110°C, then the temperature T B The temperature may be 90°C or higher and 160°C or lower.
[0123] Furthermore, in order to maintain the resin-coated magnetic particles at a temperature T B , the temperature of the fluidizing gas in the fluidized bed apparatus, the jacket temperature of the fluidized bed apparatus, or both may be adjusted.
[0124] Temperature T B The determination was as follows.
[0125] That is, with respect to temperature T B A thermometer is provided at the upper part of the fluidizing device or at the exhaust pipe of the fluidizing gas to measure the temperature of the gas immediately after the resin-coated magnetic particles are fluidized.
[0126] In addition, regarding the temperature T in step A A and the temperature T in process B B, as long as they both satisfy the range of the glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower, they may be the same temperature or different temperatures.
[0127] From the viewpoint of further improving the color fading suppression of the obtained image, for example, the temperature T in step A A and the temperature T in process B B The difference is preferably 15° C. or less, and more preferably 10° C. or less. This is because the effect of suppressing color fading of an image can be obtained in a shorter time as there is no temperature difference.
[0128] From the viewpoint of further improving the color fading suppression of the obtained image, the temperature T B For example, it is preferable to satisfy the glass transition temperature of Tg-20°C or higher and the glass transition temperature of Tg+20°C or lower, and it is more preferable to satisfy the glass transition temperature of Tg-15°C or higher and the glass transition temperature of Tg°C or lower. This is because, similar to step A, if excessive stirring workload is applied at a temperature from the glass transition temperature Tg to 50°C or higher, the resin coating layer formed on the surface of the magnetic particles will be peeled off, so it is preferably near Tg, for example.
[0129] From the viewpoint of further improving the color fading suppression of the obtained image, the temperature T is maintained at B The flow time of the resin coated magnetic particles in the state of , from the viewpoint of the fixation of the resin coating layer, there is a correlation between temperature and flow time. The higher the temperature, the shorter the time can be, but for example, it is preferably more than 20 minutes, more preferably more than 30 minutes, and further preferably more than 45 minutes.
[0130] And, about maintaining the temperature T B The upper limit of the flow time of the resin-coated magnetic particles in the state is 360 minutes, and preferably 120 minutes or less, because there is a concern that the amount of free resin in the resin coating layer will increase due to the contact between the resin-coated magnetic particles during flow.
[0131] Maintaining the temperature T B The flow time of the resin-coated magnetic particles in the state is, for example, preferably from 20 minutes to 120 minutes, more preferably from 30 minutes to 90 minutes, and further preferably from 45 minutes to 60 minutes.
[0132] <Process C>
[0133] The method for producing a carrier for electrostatic latent image development according to the present embodiment includes a cooling step C of cooling the resin-coated magnetic particles after the step B. The step C is preferably performed after the step B in a fluidized bed apparatus, for example.
[0134] Here, the cooling temperature of the resin-coated magnetic particles is, for example, preferably not more than the glass transition temperature Tg-30° C., more preferably not more than the glass transition temperature Tg-40° C. The lower limit of the cooling temperature of the resin-coated magnetic particles is room temperature, for example, 20° C.
[0135] Here, the cooling temperature refers to the temperature reached by the resin-coated magnetic particles due to cooling in the fluidized bed apparatus.
[0136] In the present embodiment, from the viewpoint of further improving the color fading suppression of the obtained image, for example, it is preferred that in step B, the resin-coated magnetic particles after step A are maintained at a temperature T B In step C, the temperature T of the resin-coated magnetic particles is lowered to C Cool to below the glass transition temperature Tg-40°C.
[0137] Furthermore, there is no particular restriction on the cooling time of the resin-coated magnetic particles, but from the viewpoint of the manufacturing speed of the carrier and the color fading suppression of the obtained image, it is preferably from 10 minutes to 360 minutes, more preferably from 30 minutes to 240 minutes, and particularly preferably from 60 minutes to 150 minutes.
[0138] A fluidized bed apparatus is used in step B and step C. By fluidizing the resin-coated magnetic particles with a fluidized bed apparatus capable of non-stirring mixing and further cooling them, fixation of the resin coating layer to the magnetic particles can be promoted.
[0139] The fluidized bed apparatus may be a fluidized bed apparatus that merely flows air or a vibrating fluidized bed apparatus that assists fluidization by vibration, but is not particularly limited.
[0140] The fluidized bed apparatus is capable of discharging the resin-coated magnetic particles from the bottom of the apparatus and the temperature is controlled to the above temperature T. B or T C In other words, the fluidized bed apparatus has a mechanism for heating or cooling the gas.
[0141] As a mechanism for heating the gas, an air heater or the like can be cited. For example, the gas is heated to a temperature T by using an air heater provided outside the main body of the fluidized bed apparatus. BThe gas is supplied to the bottom of the device, which enables the resin-coated magnetic particles to be maintained at a temperature T B flows in the state of.
[0142] The mechanism for cooling the gas is not particularly limited, and the resin-coated magnetic particles can be cooled (for example, to a glass transition temperature Tg-40° C. or less) by supplying a room temperature gas to the bottom of the device.
[0143] Furthermore, the main body of the fluidized bed apparatus may be provided with a jacket structure so that hot water or cooling water circulates to heat or cool the gas.
[0144] For example, step B is preferably performed continuously after step A.
[0145] Specifically, for example, it is preferred that the resin-coated magnetic particles that have been decomposed and pulverized in step A are directly introduced from the mixer into the fluidized bed apparatus.
[0146] The temperature of the resin-coated magnetic particles using the fluidized bed device can be adjusted by the conduction heat transfer efficiency determined by the stirring state in the tank based on the temperature of the resin-coated magnetic particles put into the device, the temperature of the fluidizing gas, and the superficial velocity of the fluidizing gas based on the minimum fluidizing velocity Umf described later. For example, the higher the temperature of the fluidizing gas and the faster the superficial velocity, the faster the temperature of the resin-coated magnetic particles can be raised in a short time.
[0147] The fluidized bed apparatus is maintained at a temperature T B When the resin-coated magnetic particles are made to flow in a state of T, it is preferable to reduce the friction between the resin-coated magnetic particles or reduce the shear force on the resin-coated magnetic particles from the gas. This is because if the temperature T B When the temperature is higher than the glass transition temperature Tg, the resin-coated magnetic particles are easily affected by the stress such as the friction and shear force, and the resin coating layer is easily peeled off.
[0148] In order to reduce the friction between the resin-coated magnetic particles or reduce the shear force on the resin-coated magnetic particles from the gas, the decomposed and pulverized resin-coated magnetic particles are kept at a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H (m / s) can be set to a smaller value.
[0149] Specifically, in step B, the resin-coated magnetic particles after step A are maintained at a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H(m / s) is, for example, preferably at least 1 time and no more than 5 times the minimum fluidization velocity Umf, and more preferably at least 2 times and no more than 3 times the minimum fluidization velocity Umf.
[0150] The minimum fluidization velocity Umf can be obtained by the following equation from the flow rate at the point where the pressure of the fluidizing gas begins to stabilize after experimentally increasing the pressure.
[0151] Minimum fluidization velocity Umf (m / s) = flow rate at the change point (m 3 / s)÷cross-sectional area of fluidizing device (m 2 )
[0152] Then, the resin-coated magnetic particles are maintained at a temperature T B The superficial velocity V of the fluidizing gas when flowing in the state H The speed is not particularly limited, but is preferably 10 mm / s to 50 mm / s, and more preferably 20 mm / s to 30 mm / s.
[0153] Furthermore, from the viewpoint of improving cooling efficiency, the superficial velocity V of the fluidizing gas in the fluidized bed device when cooling the resin-coated magnetic particles is 2.5 V. C (m / s) is, for example, preferably at least 2 times and at most 10 times the minimum fluidization velocity Umf, and more preferably at least 5 times and at most 10 times the minimum fluidization velocity Umf.
[0154] In addition, from the viewpoint of improving cooling efficiency, for example, the superficial velocity V of the fluidizing gas in the fluidized bed device when cooling the resin-coated magnetic particles is set to C (m / s) is preferably greater than the temperature at which the resin-coated magnetic particles are maintained at T B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H (m / s).
[0155] The fluidizing gas in the fluidizing device is not particularly limited, and air, nitrogen, argon, etc. can be used. Among them, air is preferred, for example.
[0156] Furthermore, the fluidizing gas is preferably, for example, a dehumidified gas, preferably a gas having a relative humidity of 30% or less, more preferably a gas having a relative humidity of 20% or less, and particularly preferably a gas having a relative humidity of 10% or less.
[0157] By going through the above steps A, B, and C, a carrier for developing an electrostatic latent image having a resin coating layer on the surface of magnetic particles can be obtained.
[0158] <Other Process>
[0159] The method for producing a carrier for electrostatic latent image development according to the present embodiment may include other steps besides step A, step B, and step C.
[0160] The other steps are not particularly limited, and may include known steps in the method for producing a carrier for developing an electrostatic latent image.
[0161] The method for producing a carrier for electrostatic latent image development according to the present embodiment preferably further includes, for example, a step of preparing magnetic particles and a step of preparing a mixed solution containing a resin and a solvent.
[0162] <Physical properties of carrier>
[0163] The volume average particle size of the electrostatic latent image developing carrier obtained by the method for producing an electrostatic latent image developing carrier according to the present embodiment is, for example, preferably 10 μm to 500 μm, more preferably 15 μm to 100 μm, and particularly preferably 20 μm to 60 μm.
[0164] The volume average particle size of the magnetic particles and the carrier in this embodiment is set to the value measured by the laser diffraction particle size distribution measuring device LA-700 (manufactured by HORIBA, Ltd.) Specifically, for the particle size range (channel) obtained by dividing the particle size distribution obtained by the measuring device, the volume cumulative distribution is drawn from the small particle size side and the particle size when the cumulative value reaches 50% is set as the volume average particle size.
[0165] From the viewpoint of thickness stability and chargeability of the resin coating layer, the amount of the resin coating layer in the electrostatic latent image developing carrier obtained by the method for manufacturing an electrostatic latent image developing carrier involved in this embodiment is preferably greater than 0.5 mass % and less than 10 mass %, and more preferably greater than 1 mass % and less than 5 mass %, relative to the total mass of the carrier.
[0166] From the perspective of suppressing color dullness of the obtained image, the amount of free resin in the electrostatic latent image developing carrier obtained by the method for manufacturing an electrostatic latent image developing carrier involved in this embodiment is, for example, preferably less than 300 ppm, more preferably less than 100 ppm, further preferably less than 50 ppm, and particularly preferably less than 30 ppm.
[0167] The method for measuring the amount of free resin in the electrostatic latent image developing carrier in the present embodiment is as follows.
[0168] A certain amount of the carrier was weighed and dispersed in water, and the dispersion was filtered while the carrier was fixed with a magnet. The filter paper was dried, and the free resin amount was calculated by the following formula based on the difference in mass before and after the filter paper and the amount of the carrier weighed.
[0169] Free resin amount (ppm) = filter paper increase (g) ÷ carrier (g)
[0170] The smaller the proportion of agglomerates after 75 μm sieving in the electrostatic latent image developing carrier obtained by the manufacturing method of the electrostatic latent image developing carrier involved in this embodiment, the better. From the viewpoint of color dullness suppression of the obtained image, it is, for example, preferably less than 5% by number, more preferably less than 1% by number, further preferably less than 0.1% by number, and particularly preferably less than 0.01% by number.
[0171] The method for measuring the ratio of aggregates after 75 μm sieving in the carrier for electrostatic latent image development in the present embodiment is as follows.
[0172] The carriers were sieved using a sieve with a pore size of 75 μm. The sieved carriers were spread out in a manner that did not overlap as much as possible, and a 350-fold scanning electron microscope (SEM) photograph was taken to measure the ratio of the number of carriers that were not decomposed and crushed to primary particles relative to the number of carriers in one field of view.
[0173] The exposed area ratio of the magnetic particles in the carrier for electrostatic latent image development in this embodiment is, for example, preferably 3% or more and 30% or less, more preferably 4% or more and 25% or less, and further preferably 5% or more and 20% or less. The exposed area ratio of the magnetic particles in the carrier can be controlled by the amount of resin used to form the resin coating layer. The greater the amount of resin relative to the amount of magnetic particles, the smaller the exposed area ratio.
[0174] That is, the coverage of the resin coating layer on the surface of the electrostatic latent image developing carrier in this embodiment is, for example, preferably 70% to 97%, more preferably 75% to 96%, and further preferably 80% to 95%.
[0175] The exposed area ratio of the magnetic particles and the coverage ratio of the resin coating layer on the surface of the carrier are values obtained by the following method.
[0176] Prepare a carrier as a target and magnetic particles after removing the resin coating from the carrier as a target. As a method for removing the resin coating from the carrier, for example, there are a method of removing the resin coating by dissolving the resin component with an organic solvent, a method of removing the resin coating by heating at about 800°C to make the resin component disappear, etc. The carrier and the magnetic particles are respectively used as measurement samples, and the ratio (atomic %) of Fe, C, and O on the surface of the sample is quantified by XPS, and (Fe ratio of the carrier) ÷ (Fe ratio of the magnetic particles) × 100 is calculated as the exposed area ratio (%) of the magnetic particles.
[0177] The coverage rate (%) of the resin coating layer was determined by (100 - exposed area rate of the magnetic particles).
[0178] From the viewpoint of suppressing concentration changes in the obtained image, the fluidity of the carrier for electrostatic latent image development in the present embodiment is, for example, preferably from 20 sec / 50 g to 50 sec / 50 g, more preferably from 22 sec / 50 g to 35 sec / 50 g, and particularly preferably from 25 sec / 50 g to 30 sec / 50 g.
[0179] The fluidity of the electrostatic latent image developing carrier in the present embodiment is a value measured at 25° C. and 50% RH in accordance with JIS Z 2502 (2020).
[0180] <Structure of carrier>
[0181] The carrier for electrostatic latent image development obtained by the method for producing a carrier for electrostatic latent image development according to the present embodiment has a resin coating layer on the surface of magnetic particles.
[0182] Hereinafter, the structure of the electrostatic latent image developing carrier in this embodiment will be described.
[0183] [Magnetic particles]
[0184] As the magnetic particles used in this embodiment, known magnetic particles are used.
[0185] As the magnetic particles, known materials are used, for example, magnetic metals such as iron, nickel, and cobalt, alloys of these magnetic metals with manganese, chromium, and rare earth elements, magnetic oxides such as iron oxide, ferrite, and magnetite, and resin-dispersed magnetic particles in which a conductive material is dispersed in a matrix resin.
[0186] Examples of the resin used in the resin-dispersed magnetic particles include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylic acid copolymer, straight-chain silicone resin containing an organic siloxane bond or a modified product thereof, fluororesin, polyester, polycarbonate, phenolic resin, epoxy resin, etc., but are not limited to these.
[0187] Among them, as the magnetic particles, for example, magnetic oxide particles are preferred, and ferrite particles are more preferred.
[0188] -Ferrite particles-
[0189] Ferrites are usually made of (MO) X (Fe2O3) YIn the formula, M is mainly Mn, but can also be combined with at least one or more selected from the group consisting of Li, Ca, Sr, Sn, Cu, Zn, Ba, Fe, Ti, Ni, Al, Co and Mo. In addition, X and Y represent molar ratios and satisfy the condition X+Y=100. Generally, the properties of ferrite particles vary depending on their composition and structure.
[0190] The ferrite particles used in the present embodiment are not particularly limited, but can be produced, for example, as follows.
[0191] Powders of metal oxides or metal salts as raw materials are mixed and pre-calcined using a rotary kiln or the like to obtain a pre-calcined product. Here, as the metal oxides or metal salts as raw materials, Fe2O3, MnO2, SrCO3, Mg(OH)2, etc. can be cited. For example, by adjusting the amount of SrCO3, the content of strontium in the ferrite particles is set to 0.1 mass % or more and 1.0 mass % or less. In addition, the pre-calcination temperature can be 800°C or more and 1,000°C or less, and the pre-calcination time can be 6 hours or more and 10 hours or less. The obtained pre-calcined product is pulverized by a known pulverization method. Specifically, polyvinyl alcohol and water, a surfactant, and a defoaming agent are added, and pulverized using a mortar, a ball mill, a jet mill, etc. The pulverization of the pre-calcined product is performed, for example, until the average particle size becomes 4 μm or more and 10 μm or less. Next, the pulverized pre-calcined product is granulated with a spray dryer and dried. The dried pre-calcined product is pre-calcined again (second pre-calcination) to remove the organic matter and obtain the second pre-calcined product. The temperature of the second pre-calcination can be 800°C or more and 1,000°C or less, and the time of the second pre-calcination can be 5 hours or more and 10 hours or less. Polyvinyl alcohol and water, a surfactant, and a defoaming agent are added to the obtained second pre-calcined product, and the product is crushed using a mortar, a ball mill, a jet mill, etc. The second pre-calcined product is crushed, for example, until the average particle size becomes 4 μm or more and 8 μm or less. Then, the crushed second pre-calcined product is granulated with a spray dryer and dried. The dried granulated product is calcined (formal calcination) using a rotary kiln or the like to obtain the calcined product. Here, the temperature of the formal calcination can be 1,000°C or more and 1,400°C or less, and the time of the formal calcination can be 3 hours or more and 6 hours or less. The formal calcined product is then subjected to a decomposition and crushing step and a classification step to obtain ferrite particles.
[0192] The volume average particle size of the magnetic particles used in the present embodiment is, for example, preferably 10 μm or more and 500 μm or less, more preferably 15 μm or more and 100 μm or less, and particularly preferably 20 μm or more and 60 μm or less.
[0193] The average particle size of the calcined product or ferrite particles refers to a value measured using a laser diffraction / scattering particle size distribution analyzer (LS Particle Size Analyzer: LS13 320, manufactured by BECKMAN COULTER, INC.). For the particle size range (channel) obtained by dividing the obtained particle size distribution, the cumulative distribution is plotted from the small particle size side, and the particle size when the cumulative value reaches 50% is defined as the volume average 50% particle size.
[0194] From the viewpoint of long-term image quality stability and concentration change suppression, the value of the BET specific surface area of the magnetic particles is preferably 0.10 m 2 / g or more and 0.35m 2 / g or less, more preferably 0.11m 2 / g or more and 0.28m 2 / g or less, particularly preferably 0.12m 2 / g or more and 0.24m 2 In addition, within the above range, an appropriate amount of coating resin enters the gaps between the magnetic particles, and degradation of the resin coating layer due to the anchoring effect can be suppressed, resulting in excellent long-term image quality stability and concentration change suppression.
[0195] The BET specific surface area of the magnetic particles was measured by the nitrogen substitution three-point method using an SA3100 specific surface area measuring apparatus (manufactured by Beckman Coulter, Inc.) Specifically, 5 g of the magnetic particles were placed in a dish and degassed at 60° C. for 120 minutes using a mixed gas of nitrogen and helium (30:70).
[0196] As a method for separating magnetic particles from a carrier, more specifically, for example, 20 g of a resin-coated carrier is placed in 100 mL of toluene. Ultrasonic waves are irradiated at 40 kHz for 30 seconds. Depending on the particle size, any filter paper is used to separate the magnetic particles and the resin solution. 20 mL of toluene is poured from above on the magnetic particles remaining on the filter paper to wash them. Next, the magnetic particles remaining on the filter paper are recovered. Similarly, the recovered magnetic particles are placed in 100 mL of toluene and irradiated at 40 kHz for 30 seconds. Similarly, they are filtered, washed with 20 mL of toluene, and then recovered. This step is performed 10 times in total. Finally, the recovered magnetic particles are dried, and the BET specific surface area is measured under the above conditions.
[0197] The arithmetic mean height Ra (JIS B0601:2001) of the roughness curve of the magnetic particles is, for example, preferably 0.1 μm or more and 1 μm or less, and more preferably 0.2 μm or more and 0.8 μm or less.
[0198] The arithmetic mean height Ra of the roughness curve of the magnetic particles is obtained by observing the magnetic particles at an appropriate magnification (e.g., 1000 times) using a surface shape measuring device (e.g., "Ultra-deep Color 3D Shape Measurement Microscope VK-9700" manufactured by KEYENCE CORPORATION), obtaining a roughness curve with a cutoff value of 0.08 mm, and extracting a reference length of 10 μm from the roughness curve in the direction of its average line. The Ra of 100 magnetic particles is arithmetic averaged.
[0199] Regarding the magnetic force of magnetic particles, the saturation magnetization under a magnetic field of 3,000 oersted is preferably, for example, 50emu / g or more, and more preferably 60emu / g or more. The above-mentioned saturation magnetization is measured using a vibrating sample type magnetometer VSMP10-15 (manufactured by TOEI INDUSTRY CO., LTD.). The measurement sample is placed in a dish with an inner diameter of 7mm and a height of 5mm and is set in the device. During the measurement, the magnetic field is applied and scanned to a maximum of 3000 oersted. Then, the applied magnetic field is reduced and a hysteresis curve is made on a recording paper. The saturation magnetization, residual magnetization, and coercive force are obtained based on the data of the curve.
[0200] The volume resistance (volume resistivity) of the magnetic particles is preferably, for example, 1×10 5 Ω·cm or more and 1×10 9 Ω·cm or less, more preferably 1×10 7 Ω·cm or more and 1×10 9 Ω·cm or less.
[0201] The volume resistivity (Ω·cm) of the magnetic particles is measured as follows. The object to be measured is placed flat on a 20 cm 2 The electrode plate is placed on the surface of the circular fixture to form a layer. 2 The electrode plates are used to sandwich the layers. In order to eliminate the gaps between the objects to be measured, a load of 4 kg is applied to the electrode plates arranged on the layers, and then the thickness of the layers (cm) is measured. An electrometer and a high-voltage power supply generator are connected to the upper and lower electrodes of the layers. A high voltage is applied to the two electrodes so that the electric field becomes 103.8 V / cm, and the current value (A) flowing at this time is read. The measurement environment is set to a temperature of 20°C and a relative humidity of 50%. The calculation formula for the volume resistivity (Ω·cm) of the object to be measured is shown below.
[0202] R=E×20 / (I-I0) / L
[0203] In the above formula, R represents the volume resistance of the object to be measured (Ω·cm), E represents the applied voltage (V), I represents the current value (A), I0 represents the current value (A) at an applied voltage of 0V, and L represents the thickness of the layer (cm). The coefficient 20 represents the area of the electrode plate (cm 2 ).
[0204] [Resin coating]
[0205] The electrostatic latent image developing carrier in this embodiment has a resin coating layer that coats magnetic particles.
[0206] The resin constituting the resin coating layer includes styrene-acrylic acid copolymer; polyolefin resins such as polyethylene and polypropylene; polyvinyl or polyvinylidene resins such as polystyrene, acrylic resin, polyacrylonitrile, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl carbazole, polyvinyl ether, and polyvinyl ketone; vinyl chloride-vinyl acetate copolymer; straight-chain silicone resin containing an organic siloxane bond or a modified product thereof; fluororesins such as polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride, and polychlorotrifluoroethylene; polyester; polyurethane; polycarbonate; amino resins such as urea-formaldehyde resin; epoxy resin, etc.
[0207] Among them, from the viewpoints of charging properties, controllability of external additive adhesion and suppression of concentration changes, the resin constituting the resin coating layer preferably contains an acrylic resin, for example, more preferably contains 50% by mass or more of acrylic resin relative to the total mass of the resin in the resin coating layer, and particularly preferably contains 80% by mass or more of acrylic resin relative to the total mass of the resin in the resin coating layer.
[0208] From the viewpoint of concentration variation inhibition, the resin coating layer preferably contains an acrylic resin having an alicyclic structure, for example. As the polymerization component of the acrylic resin having an alicyclic structure, for example, a lower alkyl ester of (meth) acrylic acid (for example, an alkyl (meth) acrylic acid ester having a carbon number of 1 or more and 9 or less), specifically, methyl (meth) acrylate, ethyl (meth) acrylate, propyl (meth) acrylate, butyl (meth) acrylate, hexyl (meth) acrylate, cyclohexyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, etc. can be cited. These monomers can be used alone or in combination.
[0209] The acrylic resin having an alicyclic structure preferably contains, for example, cyclohexyl (meth)acrylate as a polymerized component. The content of the monomer unit derived from cyclohexyl (meth)acrylate contained in the acrylic resin having an alicyclic structure is, for example, preferably 75% by mass or more and 100% by mass or less, more preferably 85% by mass or more and 100% by mass or less, and further preferably 95% by mass or more and 100% by mass or less, relative to the total mass of the acrylic resin having an alicyclic structure.
[0210] The weight average molecular weight of the resin contained in the resin coating layer is, for example, preferably less than 300,000, more preferably less than 250,000, further preferably 5,000 or more and less than 250,000, and particularly preferably 10,000 or more and 200,000 or less. Within the above range, the smoothness of the resin-coated surface of the carrier is improved, so the amount of external additives attached to the carrier is reduced, and the concentration change suppression property is more excellent.
[0211] The resin coating layer may contain conductive particles for the purpose of controlling charging or resistance. Examples of the conductive particles include carbon black and conductive particles among inorganic particles described below. Among them, carbon black is preferred.
[0212] From the viewpoint of chargeability, the content of the conductive particles contained in the resin coating layer is, for example, preferably greater than 0.1 mass % and less than 30 mass %, more preferably greater than 0.5 mass % and less than 20 mass %, and further preferably greater than 1 mass % and less than 10 mass %, relative to the total mass of the resin coating layer.
[0213] Furthermore, the resin coating layer may contain inorganic particles.
[0214] Examples of the inorganic particles contained in the resin coating layer include metal oxide particles such as silicon dioxide, titanium oxide, zinc oxide, and tin oxide; metal compound particles such as barium sulfate, aluminum borate, and potassium titanate; and metal particles such as gold, silver, and copper.
[0215] Among these, from the viewpoint of suppressing concentration change, for example, silica particles are preferred.
[0216] From the viewpoint of suppressing concentration changes, the arithmetic mean particle size of the inorganic particles in the resin coating layer is, for example, preferably from 5 nm to 90 nm, more preferably from 5 nm to 70 nm, further preferably from 5 nm to 50 nm, and particularly preferably from 8 nm to 50 nm.
[0217] In the present embodiment, the average particle size of the inorganic particles contained in the resin coating layer is determined by the following method.
[0218] The carrier is embedded with epoxy resin and cut with a slicer to make a carrier cross section. The SEM image obtained by taking the carrier cross section with a scanning electron microscope (SEM) is read into an image processing and analysis device for image analysis. 100 inorganic particles (primary particles) in the resin coating layer are randomly selected, and their respective equivalent circle diameters (nm) are calculated and arithmetic averaged, which is used as the average particle size (nm) of the inorganic particles.
[0219] The surface of inorganic particles can implement hydrophobic treatment.As hydrophobic treatment agent, for example, known organosilicon compounds with alkyl (for example, methyl, ethyl, propyl, butyl, etc.) can be enumerated, and in specific examples, alkoxysilane compounds, siloxane compounds, silazane compounds, etc. can be enumerated.In these, hydrophobic treatment agent, for example, is preferably silazane compound, preferably hexamethyldisilazane.Hydrophobic treatment agent can be used alone one, it is also possible to use two or more simultaneously.
[0220] As a method for hydrophobizing inorganic particles using a hydrophobizing agent, for example, the following method can be cited: using supercritical carbon dioxide to dissolve the hydrophobizing agent in supercritical carbon dioxide so that the hydrophobizing agent adheres to the surface of the inorganic particles; in the atmosphere, applying (for example, spraying or coating) a solution containing the hydrophobizing agent and a solvent that dissolves the hydrophobizing agent to the surface of the inorganic particles so that the hydrophobizing agent adheres to the surface of the inorganic particles; in the atmosphere, after adding a solution containing the hydrophobizing agent and a solvent that dissolves the hydrophobizing agent to an inorganic particle dispersion and maintaining it, the mixed solution of the inorganic particle dispersion and the solution is dried.
[0221] From the viewpoint of suppressing concentration changes, the content of inorganic particles contained in the resin coating layer is, for example, preferably greater than 10 mass % and less than 60 mass %, more preferably greater than 15 mass % and less than 55 mass %, and further preferably greater than 20 mass % and less than 50 mass %, relative to the total mass of the resin coating layer.
[0222] The solvent used for forming the resin coating layer is not particularly limited as long as it dissolves or disperses the resin, and examples thereof include aromatic hydrocarbons such as toluene and xylene; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran and dioxane; and the like.
[0223] Among them, toluene can be mentioned.
[0224] The solid content of the mixed solution for forming the resin coating layer is not particularly limited, but is preferably 5% by mass or more and 50% by mass or less, and more preferably 10% by mass or more and 30% by mass or less.
[0225] Furthermore, the mixed liquid may contain conductive particles, inorganic particles, and the like, or in step A, conductive particles, inorganic particles, and the like may be added separately to the mixed liquid.
[0226] The average thickness of the resin coating layer is, for example, preferably 0.1 μm or more and 10 μm or less, more preferably 0.2 μm or more and 5 μm or less, and further preferably 0.3 μm or more and 3 μm or less.
[0227] The average thickness of the resin coating layer is measured by the following method. The carrier is embedded in an epoxy resin or the like, and cut with a diamond knife or the like to make a thin section. The thin section is observed with a transmission electron microscope (TEM) or the like, and a cross-sectional image of a plurality of carrier particles is taken. The thickness of the resin coating layer at 20 locations is measured from the cross-sectional image of the carrier particles, and the average value thereof is adopted.
[0228] <<Method for producing electrostatic latent image developer>>
[0229] The method for producing an electrostatic latent image developer according to the present embodiment includes the method for producing an electrostatic latent image developing carrier according to the present embodiment.
[0230] Specifically, the method for manufacturing an electrostatic latent image developer according to the present embodiment includes: the method for manufacturing an electrostatic latent image developing carrier according to the present embodiment; and a step of mixing the electrostatic latent image developing carrier manufactured by the method for manufacturing an electrostatic latent image developing carrier according to the present embodiment and a toner.
[0231] The electrostatic latent image developer produced by the method for producing an electrostatic latent image developer according to the present embodiment is a two-component developer including the electrostatic latent image developing carrier produced by the method for producing an electrostatic latent image developing carrier according to the present embodiment and a toner.
[0232] The mixing ratio (mass ratio) of the carrier and the toner in the developer is, for example, preferably carrier:toner=100:1 to 100:30, and more preferably 100:3 to 100:20.
[0233] <Coloring agent>
[0234] The toner contains toner particles and, if necessary, an external additive.
[0235] The toner particles contain, for example, a binder resin and, if necessary, a colorant, a release agent, and other additives.
[0236] -Bonding resin-
[0237] Examples of the binder resin include vinyl resins composed of homopolymers of monomers such as styrenes (e.g., styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (e.g., ethylene, propylene, butadiene, etc.), or copolymers of two or more of these monomers.
[0238] Examples of the binder resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosins, and mixtures thereof with the vinyl resins or graft polymers obtained by polymerizing vinyl monomers under the coexistence of the non-vinyl resins.
[0239] These binder resins may be used alone or in combination of two or more.
[0240] As the binder resin, for example, polyester resin is preferable.
[0241] As the polyester resin, for example, a known amorphous polyester resin can be cited. The polyester resin can be used together with a crystalline polyester resin. However, the crystalline polyester resin is preferably used in a range of 2% by mass or more and 40% by mass or less (for example, more preferably 2% by mass or more and 20% by mass or less) relative to the entire binder resin.
[0242] The "crystallinity" of a resin means that it has a clear endothermic peak in differential scanning calorimetry (DSC) rather than a step-like endothermic change. Specifically, it means that the half width of the endothermic peak is within 10°C when measured at a heating rate of 10 (°C / min).
[0243] On the other hand, the "amorphous" nature of a resin means that the half width exceeds 10°C, the endothermic value shows a step-like change, or a clear endothermic peak cannot be confirmed.
[0244] Amorphous polyester resin
[0245] Examples of the non-crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the non-crystalline polyester resin, a commercially available product may be used, or a synthetic resin may be used.
[0246] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), and anhydrides thereof or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.
[0247] The polycarboxylic acid may be used together with the dicarboxylic acid in a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent or higher carboxylic acid include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0248] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0249] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.
[0250] As the polyol, a trivalent or higher polyol having a cross-linked structure or a branched structure may be used together with a diol. Examples of the trivalent or higher polyol include glycerol, trimethylolpropane, and pentaerythritol.
[0251] The polyols may be used alone or in combination of two or more.
[0252] The glass transition temperature (Tg) of the amorphous polyester resin is, for example, preferably 50° C. or higher and 80° C. or lower, and more preferably 50° C. or higher and 65° C. or lower.
[0253] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for determining the glass transition temperature in JIS K7121:1987 "Determination of Transition Temperature of Plastics".
[0254] The weight average molecular weight (Mw) of the amorphous polyester resin is, for example, preferably 5,000 or more and 1,000,000 or less, and more preferably 7,000 or more and 500,000 or less.
[0255] The number average molecular weight (MN) of the amorphous polyester resin is preferably, for example, 2,000 or more and 100,000 or less.
[0256] The molecular weight distribution Mw / MN of the amorphous polyester resin is, for example, preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.
[0257] The weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement by GPC, GPC HLC-8120GPC manufactured by TOSOH CORPORATION is used as a measuring device, and a column TSKgel SuperHM-M (15 cm) manufactured by TOSOH CORPORATION is used, and the solvent is THF. The weight average molecular weight and the number average molecular weight are calculated using a molecular weight calibration curve prepared from a monodisperse polystyrene standard sample based on the measurement results.
[0258] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water and alcohol generated during condensation.
[0259] When the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent can be added as a cosolvent to dissolve it. In this case, the polycondensation reaction is carried out while the cosolvent is removed by distillation. When there are monomers with poor compatibility in the copolymerization reaction, for example, the monomers with poor compatibility can be condensed in advance with an acid or alcohol to be polycondensed with the monomer, and then polycondensed with the main component.
[0260] Crystalline polyester resin
[0261] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the crystalline polyester resin, a commercially available product may be used, and a synthetic resin may also be used.
[0262] Here, since the crystalline polyester resin easily forms a crystalline structure, it is preferable to use a polycondensate of a linear aliphatic polymerizable monomer rather than a polycondensate of a polymerizable monomer having an aromatic ring, for example.
[0263] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., having 1 to 5 carbon atoms) alkyl esters thereof.
[0264] The polycarboxylic acid may be used together with the dicarboxylic acid and a trivalent or higher carboxylic acid having a cross-linked structure or a branched structure. Examples of the trivalent carboxylic acid include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0265] As the polycarboxylic acid, a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond may be used together with these dicarboxylic acids.
[0266] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0267] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-docosanediol. Among these, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.
[0268] The polyol may be used together with the diol and a trivalent or higher alcohol having a cross-linked structure or a branched structure. Examples of the trivalent or higher alcohol include glycerol, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0269] The polyols may be used alone or in combination of two or more.
[0270] Among these, for example, the content of the aliphatic diol in the polyol is preferably 80 mol % or more, and more preferably 90 mol % or more.
[0271] The melting temperature of the crystalline polyester resin is, for example, preferably 50° C. or higher and 100° C. or lower, more preferably 55° C. or higher and 90° C. or lower, and further preferably 60° C. or higher and 85° C. or lower.
[0272] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121:1987 “Determination of transition temperatures of plastics”.
[0273] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably, for example, 6,000 or more and 35,000 or less.
[0274] Similar to the amorphous polyester resin, the crystalline polyester resin can be obtained by, for example, a known production method.
[0275] The content of the binder resin is, for example, preferably 40 mass % to 95 mass % inclusive, more preferably 50 mass % to 90 mass % inclusive, and further preferably 60 mass % to 85 mass % inclusive, based on the entire toner particles.
[0276] -Colorants-
[0277] Examples of the colorant include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, vulcan orange, magenta, permanent red, brilliant carmine 3B, brilliant carmine 6B, Dupont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose Bengal, aniline blue, ultramarine blue, copper oil blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate and other pigments; and dyes such as acridine, xanthene, azo, benzoquinone, azine, anthraquinone, thioindigo, dioxazine, thiazine, azomethine, indigo, phthalocyanine, nigrosine, polymethine, triphenylmethane, diphenylmethane and thiazole.
[0278] The coloring agent may be used alone or in combination of two or more.
[0279] The colorant may be a surface-treated colorant as required, or may be used together with a dispersant. Furthermore, multiple colorants may be used together.
[0280] The content of the colorant is, for example, preferably 1 mass % or more and 30 mass % or less, and more preferably 3 mass % or more and 15 mass % or less, based on the entire toner particles.
[0281] -Release agent-
[0282] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral / petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.
[0283] The melting temperature of the release agent is, for example, preferably 50° C. or higher and 110° C. or lower, and more preferably 60° C. or higher and 100° C. or lower.
[0284] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) in accordance with the “melting peak temperature” described in the method for determining the melting temperature in JIS K7121:1987 “Determination of transition temperatures of plastics”.
[0285] The content of the releasing agent is, for example, preferably 1 mass % or more and 20 mass % or less, and more preferably 5 mass % or more and 15 mass % or less, based on the entire toner particles.
[0286] -Other additives-
[0287] Examples of other additives include known additives such as magnetic materials, charge control agents, and inorganic powders. These additives are contained in the toner particles as internal additives.
[0288] -Characteristics of toner particles, etc.-
[0289] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core / shell structure composed of a core (core particle) and a coating layer (shell layer) that covers the core.
[0290] The toner particles of the core / shell structure preferably include, for example, a core portion that contains a binder resin and, if necessary, contains other additives such as a colorant and a release agent, and a coating layer that contains a binder resin.
[0291] The volume average particle diameter (D50v) of the toner particles is, for example, preferably 2 μm or more and 10 μm or less, and more preferably 4 μm or more and 8 μm or less.
[0292] The volume average particle size (D50v) of the toner particles is measured using Coulter Multisizer II (manufactured by Beckman Coulter, Inc.), and the electrolyte solution is measured using ISOTON-II (manufactured by Beckman Coulter, Inc.).
[0293] During measurement, 0.5 mg to 50 mg of a measurement sample is added as a dispersant to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate), and this is added to 100 ml to 150 ml of an electrolyte.
[0294] The electrolyte in which the sample is suspended is dispersed for 1 minute by an ultrasonic disperser, and the particle size distribution of particles with a particle size of 2 μm or more and 60 μm or less is measured by a Coulter Multisizer II using a hole with an aperture of 100 μm. The number of particles to be sampled is 50,000. The volume-based particle size distribution is depicted from the small diameter side, and the particle size accumulated to 50% is set as the volume average particle size D50v.
[0295] The average circularity of the toner particles is, for example, preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0296] The average circularity of the toner particles is calculated by (circle equivalent circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.
[0297] First, the toner particles to be measured are collected by suction to form a flat flow, and the particle image is captured as a still image by flashing it momentarily, and the particle image is analyzed by a flow particle image analyzer (FPIA-3000 manufactured by Sysmex Corporation) to obtain the average circularity. The number of samples for obtaining the average circularity is set to 3500.
[0298] When the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant and then subjected to ultrasonic treatment to obtain toner particles from which the external additive has been removed.
[0299] -Method for producing toner particles-
[0300] The toner particles can be produced by any of dry methods (e.g., kneading and pulverization methods) and wet methods (e.g., aggregation method, suspension polymerization method, dissolution suspension method, etc.). The methods are not particularly limited to these methods, and known methods can be used. Among these, it is preferred to obtain the toner particles by, for example, the aggregation method.
[0301] Specifically, for example, in the case of manufacturing toner particles by an agglomeration method, the toner particles are manufactured through the following steps: a step of preparing a resin particle dispersion in which resin particles serving as a binding resin are dispersed (resin particle dispersion preparation step); a step of agglomerating resin particles (and other particles as needed) in the resin particle dispersion (in a dispersion after mixing other particle dispersions as needed) to form agglomerated particles (agglomerated particle formation step); and a step of heating the agglomerated particle dispersion in which the agglomerated particles are dispersed to melt / combine the agglomerated particles to form toner particles (melting / combining step).
[0302] Hereinafter, the details of each step will be described.
[0303] In the following description, a method for obtaining toner particles containing a colorant and a release agent is described, but the colorant and the release agent are used as necessary. Of course, other additives besides the colorant and the release agent may also be used.
[0304] -Resin particle dispersion preparation step-
[0305] For example, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared together with a resin particle dispersion in which resin particles serving as a binder resin are dispersed.
[0306] The resin particle dispersion is prepared by dispersing the resin particles in a dispersion medium using a surfactant, for example.
[0307] As a dispersion medium used for the resin particle dispersion, an aqueous medium is mentioned, for example.
[0308] Examples of the aqueous medium include water such as distilled water and deionized water, and alcohols, etc. These may be used alone or in combination of two or more.
[0309] As surfactants, for example, anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols, etc. can be cited. Among these, anionic surfactants and cationic surfactants can be cited in particular. Nonionic surfactants can also be used simultaneously with anionic surfactants or cationic surfactants.
[0310] The surfactant may be used alone or in combination of two or more.
[0311] In the resin particle dispersion, as a method for dispersing the resin particles in the dispersion medium, for example, common dispersion methods such as a rotary shearing homogenizer, a ball mill with a medium, a sand mill, and a Dyno-Mill can be cited. In addition, depending on the type of resin particles, the resin particles can be dispersed in the dispersion medium by a phase inversion emulsification method. The phase inversion emulsification method refers to the following method: the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, and after adding a base to the organic continuous phase (O phase) for neutralization, an aqueous medium (W phase) is added, thereby performing a phase inversion from W / O to O / W, thereby dispersing the resin in the aqueous medium in the form of particles.
[0312] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.
[0313] The volume average particle size of the resin particles is obtained by measuring the particle size distribution using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by HORIBA, Ltd.), and the cumulative distribution of the volume is plotted for the particle size range (channel) divided from the small particle size side, and the particle size when the measurement is accumulated to 50% relative to all particles is taken as the volume average particle size D50v. The volume average particle size of particles in other dispersions is also measured in the same manner.
[0314] The content of the resin particles contained in the resin particle dispersion is, for example, preferably 5 mass % or more and 50 mass % or less, and more preferably 10 mass % or more and 40 mass % or less.
[0315] In the same manner as the resin particle dispersion, for example, a colorant particle dispersion and a release agent particle dispersion are also prepared. That is, the volume average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the content of the particles are also applied to the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0316] - Agglomerated Particle Formation Step-
[0317] Next, the resin particle dispersion, the colorant particle dispersion, and the release agent particle dispersion are mixed.
[0318] Then, the resin particles, the colorant particles, and the releasing agent particles are heterogeneously aggregated in the mixed dispersion to form aggregated particles containing the resin particles, the colorant particles, and the releasing agent particles and having a diameter close to the target toner particle diameter.
[0319] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to be acidic (for example, a pH of 2 or more and 5 or less), and after a dispersion stabilizer is added as needed, it is heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles is -30°C or more and the glass transition temperature is -10°C or less), so that the particles dispersed in the mixed dispersion are agglomerated to form agglomerated particles.
[0320] In the agglomerated particle formation step, for example, the mixed dispersion may be stirred using a rotary shearing homogenizer, a coagulant may be added at room temperature (e.g., 25° C.), the pH of the mixed dispersion may be adjusted to be acidic (e.g., a pH of 2 or more and 5 or less), a dispersion stabilizer may be added as needed, and then the mixture may be heated.
[0321] Examples of the coagulant include surfactants having polarity opposite to that of the surfactant contained in the mixed dispersion, inorganic metal salts, and divalent or higher metal complexes. When a metal complex is used as the coagulant, the amount of surfactant used can be reduced, thereby improving the charging characteristics.
[0322] If necessary, an additive that forms a complex or similar bond with the metal ion of the coagulant may be used together with the coagulant. As such an additive, a chelating agent may be used.
[0323] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide; and the like.
[0324] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid; aminocarboxylic acids such as iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA); and the like.
[0325] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, relative to 100 parts by mass of the resin particles.
[0326] - Melting / combination process -
[0327] Next, the aggregated particle dispersion containing the dispersed aggregated particles is heated to, for example, a temperature not lower than the glass transition temperature of the resin particles (for example, a temperature 10° C. to 30° C. higher than the glass transition temperature of the resin particles) to melt and combine the aggregated particles to form toner particles.
[0328] Through the above steps, toner particles are obtained.
[0329] The toner particles can also be manufactured through the following steps: after obtaining an agglomerated particle dispersion in which agglomerated particles are dispersed, further mixing the agglomerated particle dispersion and a resin particle dispersion in which resin particles are dispersed, so that the agglomerated resin particles further adhere to the surface of the agglomerated particles to form second agglomerated particles; and heating the second agglomerated particle dispersion in which the second agglomerated particles are dispersed to melt / combine the second agglomerated particles to form toner particles with a core / shell structure.
[0330] After the melting / combination process is completed, the toner particles formed in the solution are subjected to a known washing process, a solid-liquid separation process, and a drying process to obtain dry toner particles. From the perspective of chargeability, the washing process is preferably performed by, for example, fully performing replacement washing with deionized water. From the perspective of productivity, the solid-liquid separation process is preferably performed by, for example, suction filtration, pressure filtration, etc. From the perspective of productivity, the drying process is preferably performed by, for example, freeze drying, airflow drying, fluidized bed drying, vibration-type fluidized bed drying, etc.
[0331] The toner used in the present embodiment is produced by, for example, adding an external additive to the obtained dry toner particles and mixing them. The mixing is preferably performed by, for example, a V mixer, a Henschel mixer, a Lödige mixer, etc. Furthermore, coarse particles of the toner can be removed by using a vibration sieving machine, a wind sieving machine, etc. as needed.
[0332] -External Additives-
[0333] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO2, TiO2, Al2O3, CuO, ZnO, SnO2, CeO2, Fe2O3, MgO, BaO, CaO, K2O, Na2O, ZrO2, CaO·SiO2, K2O·(TiO2) N , Al2O3·2SiO2, CaCO3, MgCO3, BaSO4, MgSO4, etc.
[0334] The surface of the inorganic particles as an external additive is preferably subjected to a hydrophobic treatment, for example. The hydrophobic treatment is carried out, for example, by immersing the inorganic particles in a hydrophobic treatment agent. The hydrophobic treatment agent is not particularly limited, and for example, a silane coupling agent, silicone oil, a titanate coupling agent, an aluminum coupling agent, etc. can be cited. They can be used alone or in combination of two or more.
[0335] Usually, the amount of the hydrophobizing agent is, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.
[0336] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate, melamine resin, and other resin particles), cleaning aids (for example, metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight bodies), and the like.
[0337] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.
[0338] <<Image forming apparatus, image forming method>>
[0339] The electrostatic latent image developer described above, that is, the electrostatic latent image developer including the electrostatic latent image developing carrier manufactured by the method for manufacturing the electrostatic latent image developing carrier according to the present embodiment, is applied to the image forming apparatus and the image forming method described below.
[0340] The image forming device used in this embodiment comprises: an image holder; a charging member for charging the surface of the image holder; an electrostatic latent image forming member for forming an electrostatic latent image on the surface of the charged image holder; a developing member for containing an electrostatic latent image developer and developing the electrostatic latent image formed on the surface of the image holder into a toner image using the electrostatic latent image developer; a transfer member for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing member for fixing the toner image transferred to the surface of the recording medium.
[0341] In the image forming device used in the present embodiment, an image forming method is implemented, which includes the following steps: a charging step for charging the surface of the image retaining body; an electrostatic latent image forming step for forming an electrostatic latent image on the surface of the charged image retaining body; a developing step for developing the electrostatic latent image formed on the surface of the image retaining body into a toner image using the electrostatic latent image developer involved in the present embodiment; a transfer step for transferring the toner image formed on the surface of the image retaining body to the surface of the recording medium; and a fixing step for fixing the toner image transferred to the surface of the recording medium.
[0342] The image forming device used in this embodiment applies the following well-known image forming devices: a device of a direct transfer method that directly transfers a toner image formed on the surface of an image holder to a recording medium; a device of an intermediate transfer method that transfers a toner image formed on the surface of an image holder to the surface of an intermediate transfer member for the first time, and transfers the toner image transferred to the surface of the intermediate transfer member to the surface of a recording medium for a second time; a device having a cleaning member that cleans the surface of the image holder before charging after transferring the toner image; a device having a destaticizing member that irradiates the surface of the image holder with destaticizing light to de-staticize the surface after transferring the toner image and before charging; etc.
[0343] In the case where the image forming device used in this embodiment is an intermediate transfer device, the transfer component, for example, has a structure having the following components: an intermediate transfer body having a toner image transferred on its surface; a primary transfer component that transfers the toner image formed on the surface of the image holding body to the surface of the intermediate transfer body; and a secondary transfer component that transfers the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium for the second time.
[0344] In the image forming apparatus used in the present embodiment, for example, the portion including the developing member may be a box structure (processing box) that is detachable from the image forming apparatus. As the processing box, for example, it is preferable to use a processing box having a developing member that accommodates an electrostatic latent image developer including an electrostatic latent image developing carrier manufactured by the manufacturing method of the electrostatic latent image developing carrier involved in the present embodiment.
[0345] An example of an image forming apparatus used in the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and description of other parts is omitted.
[0346] Figure 1 1 is a diagram schematically showing the configuration of an image forming apparatus used in this embodiment.
[0347] Figure 1 The image forming apparatus shown in the figure includes first to fourth image forming units 10Y, 10M, 10C, 10K (image forming members) of an electrophotographic method for outputting color images of yellow (Y), magenta (M), cyan (C), and black (K) based on color-separated image data. These image forming units (hereinafter, sometimes simply referred to as "units") 10Y, 10M, 10C, 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. These units 10Y, 10M, 10C, 10K may be process cartridges that are detachable from the image forming apparatus.
[0348] An intermediate transfer belt (an example of an intermediate transfer body) 20 is provided above each unit 10Y, 10M, 10C, and 10K so as to extend through each unit. The intermediate transfer belt 20 is provided so as to be wound around a driving roller 22 and a support roller 24 and to travel in a direction from the first unit 10Y toward the fourth unit 10K. The support roller 24 is urged in a direction away from the driving roller 22 by a spring (not shown) or the like, so that tension is applied to the intermediate transfer belt 20 wound around the two. An intermediate transfer body cleaning device 30 is provided on the image holding surface side of the intermediate transfer belt 20 so as to face the driving roller 22.
[0349] The yellow, magenta, cyan and black toners contained in the toner cartridges 8Y, 8M, 8C and 8K are respectively supplied to the developing devices (an example of developing members) 4Y, 4M, 4C and 4K of the units 10Y, 10M, 10C and 10K.
[0350] The first to fourth units 10Y, 10M, 10C, and 10K have the same structure and operation, and therefore the first unit 10Y disposed on the upstream side in the traveling direction of the intermediate transfer belt and forming a yellow image will be described as a representative.
[0351] The first unit 10Y has a photoreceptor 1Y that functions as an image holder. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging member) 2Y that charges the surface of the photoreceptor 1Y to a predetermined potential; an exposure device (an example of an electrostatic latent image forming member) 3 that forms an electrostatic latent image by exposing the charged surface using a laser beam 3Y based on a color-separated image signal; a developing device (an example of a developing member) 4Y that supplies charged toner to the electrostatic latent image to develop the electrostatic latent image; a primary transfer roller 5Y (an example of a primary transfer member) that transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning member) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.
[0352] The primary transfer roller 5Y is arranged inside the intermediate transfer belt 20 and is disposed at a position opposite to the photoreceptor 1Y. A bias power supply (not shown) for applying a primary transfer bias is connected to each of the primary transfer rollers 5Y, 5M, 5C, and 5K of each unit. Each bias power supply changes the value of the transfer bias applied to each primary transfer roller under the control of a control unit (not shown).
[0353] Next, the operation of forming a yellow image in the first unit 10Y will be described.
[0354] First, before the operation is performed, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.
[0355] The photoreceptor 1Y is conductive (for example, the volume resistivity at 20° C. is 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ω·cm or less. Usually, the photosensitive layer has a high resistance (resistance of a general resin), but has a property that the resistivity of the portion irradiated with the laser beam changes when irradiated with a laser beam. Therefore, the laser beam 3Y is irradiated from the exposure device 3 to the surface of the charged photoreceptor 1Y according to the yellow image data sent from the control unit (not shown). As a result, an electrostatic latent image of a yellow image pattern is formed on the surface of the photoreceptor 1Y.
[0356] An electrostatic latent image refers to an image formed on the surface of the photoreceptor 1Y by charging, and is a so-called negative latent image. It is formed as follows: the resistivity of the irradiated portion of the photosensitive layer is reduced by the laser beam 3Y, and the charged charge on the surface of the photoreceptor 1Y flows, while on the other hand, the charge of the portion not irradiated by the laser beam 3Y remains.
[0357] The electrostatic latent image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y travels. Then, at the development position, the electrostatic latent image on the photoreceptor 1Y is developed into a toner image by the developing device 4Y and visualized.
[0358] The developing device 4Y contains, for example, an electrostatic latent image developer containing at least a yellow toner and a carrier. The yellow toner is frictionally charged by being stirred inside the developing device 4Y, and is held on a developer roller (an example of a developer holder) with a charge of the same polarity (negative polarity) as the charge on the photoreceptor 1Y. Then, by passing the surface of the photoreceptor 1Y through the developing device 4Y, the yellow toner is electrostatically attached to the decharged latent image portion on the surface of the photoreceptor 1Y, thereby developing the latent image with the yellow toner. The photoreceptor 1Y formed with the yellow toner image continues to travel at a preset speed, so that the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.
[0359] When the yellow toner image on the photoreceptor 1Y is transferred to the primary transfer position, a primary transfer bias is applied to the primary transfer roller 5Y, and an electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, so that the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time has a (+) polarity opposite to the polarity (-) of the toner, and is controlled by a control unit (not shown) to, for example, +10 μA in the first unit 10Y.
[0360] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.
[0361] The primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled based on the first unit.
[0362] In this manner, the intermediate transfer belt 20 to which the yellow toner image has been transferred by the first unit 10Y is transported sequentially through the second to fourth units 10M, 10C, and 10K, and transfers are performed multiple times so that the toner images of the respective colors are superimposed.
[0363] The intermediate transfer belt 20 to which the toner images of four colors have been transferred multiple times through the first to fourth units arrives at a secondary transfer section composed of the intermediate transfer belt 20, a support roller 24 in contact with the inner surface of the intermediate transfer belt 20, and a secondary transfer roller (an example of a secondary transfer member) 26 disposed on the image holding surface side of the intermediate transfer belt 20. On the other hand, at a preset timing, a recording paper (an example of a recording medium) P is supplied to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 via a supply mechanism, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has a (-) polarity that is the same as the polarity (-) of the toner, and an electrostatic force from the intermediate transfer belt 20 toward the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. The secondary transfer bias at this time is determined based on the resistance detected by a resistance detection member (not shown) that detects the resistance of the secondary transfer section, and is voltage-controlled.
[0364] Then, the recording paper P is conveyed to a pressure-contact portion (nip portion) of a pair of fixing rollers of a fixing device (an example of a fixing member) 28 , and the toner image is fixed to the recording paper P, thereby forming a fixed image.
[0365] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, etc. Examples of the recording medium include, in addition to the recording paper P, OHP films, etc.
[0366] In order to further improve the smoothness of the image surface after fixing, for example, the surface of the recording paper P is preferably smooth, and for example, coated paper obtained by coating the surface of ordinary paper with a resin or the like, coated paper for printing, etc. are preferably used.
[0367] The recording paper P on which the color image has been fixed is conveyed to the discharge portion, thereby completing a series of color image forming operations.
[0368] The electrostatic latent image developer including the electrostatic latent image developing carrier manufactured by the method for manufacturing the electrostatic latent image developing carrier according to the present embodiment can be applied to a process cartridge.
[0369] The processing box used in this embodiment has a developing component, which contains an electrostatic latent image developer including an electrostatic latent image developing carrier manufactured by the manufacturing method of the electrostatic latent image developing carrier involved in this embodiment, and uses the electrostatic latent image developer to develop the electrostatic latent image formed on the surface of the image retaining body into a colorant image, and the processing box is loaded and unloaded from the image forming device.
[0370] The processing box used in this embodiment is not limited to the above-mentioned structure, and can also be a structure having a developing component and at least one component selected from other components set as needed, such as an image retaining body, a charging component, an electrostatic latent image forming component and a transfer component.
[0371] An example of a process cartridge used in the present embodiment is shown below, but the present invention is not limited thereto. In the following description, the main parts shown in the drawings are described, and description of other parts is omitted.
[0372] Figure 2 1 is a diagram schematically showing the structure of a process cartridge used in this embodiment.
[0373] Figure 2 The processing box 200 shown is constructed, for example, by combining and holding a photosensitive body 107 (an example of an image holding body), a charging roller 108 (an example of a charging component) arranged around the photosensitive body 107, a developing device 111 (an example of a developing component) and a photosensitive body cleaning device 113 (an example of an image holding body cleaning component) into an integral body through a frame 117 provided with a mounting guide 116 and an opening portion 118 for exposure, thereby forming a box.
[0374] Figure 2 109 denotes an exposure device (an example of an electrostatic latent image forming member), 112 denotes a transfer device (an example of a transfer member), 115 denotes a fixing device (an example of a fixing member), and 300 denotes recording paper (an example of a recording medium).
[0375] Example
[0376] Hereinafter, the embodiments of the present invention will be described in detail based on examples, but the embodiments of the present invention are not limited to these examples. In the following description, "parts" and "%" are based on mass unless otherwise specified.
[0377] <Production of Toner>
[0378] (Preparation of Amorphous Polyester Resin Dispersion (A1))
[0379] Ethylene glycol: 37 parts
[0380] Neopentyl glycol: 65 parts
[0381] 1,9-nonanediol: 32 parts
[0382] Terephthalic acid: 96 parts
[0383] The above materials were placed in a flask, heated to 200°C over 1 hour, and after confirming that the reaction system was uniformly stirred, 1.2 parts of dibutyltin oxide were added. While distilling off the generated water, the temperature was raised to 240°C over 6 hours, and stirring was continued at 240°C for 4 hours to obtain an amorphous polyester resin (acid value 9.4 mgKOH / g, weight average molecular weight 13,000, glass transition temperature 62°C). The amorphous polyester resin was directly transferred to an emulsifier disperser (Cavitron CD1010, EUROTEC) at a rate of 100 g per minute in a molten state. In addition, a 0.37% concentration of dilute ammonia water obtained by diluting the reagent ammonia water with deionized water was placed in a tank, heated to 120°C with a heat exchanger, and transferred to the emulsifier disperser at a rate of 0.1 liter per minute together with the amorphous polyester resin. The rotor speed was 60 Hz and the pressure was 5 kg / cm 2 The emulsifying disperser was operated under the conditions of , and an amorphous polyester resin dispersion (A1) having a volume average particle size of 160 nm and a solid content of 20% was obtained.
[0384] [Preparation of Crystalline Polyester Resin Dispersion (C1)]
[0385] Sebacic acid: 81 parts
[0386] Hexanediol: 47 parts
[0387] The above materials were placed in a flask, heated to 160°C over 1 hour, and after confirming that the reaction system was stirred uniformly, 0.03 parts of dibutyltin oxide was added. While distilling off the generated water, the temperature was raised to 200°C over 6 hours, and stirring was continued at 200°C for 4 hours. Next, the reaction liquid was cooled, solid-liquid separation was performed, and the solid matter was dried at a temperature of 40°C / under reduced pressure to obtain a crystalline polyester resin (C1) (melting point 64°C, weight average molecular weight 15,000).
[0388] Crystalline polyester resin (C1): 50 parts
[0389] Anionic surfactant (manufactured by DKS Co. Ltd., NEOGEN RK): 2 parts
[0390] Deionized water: 200 parts
[0391] The above materials were heated to 120°C, fully dispersed with a homogenizer (ULTRA TURRAX T50, IKA), and then dispersed with a pressure discharge homogenizer. When the volume average particle size reached 180 nm, the particles were recovered to obtain a crystalline polyester resin dispersion (C1) having a solid content of 20%.
[0392] [Preparation of Release Agent Particle Dispersion (W1)]
[0393] Paraffin wax (HNP-9 manufactured by NIPPON SEIRO CO., LTD.): 100 parts
[0394] Anionic surfactant (manufactured by DKS Co. Ltd., NEOGEN RK): 1 part
[0395] Deionized water: 350 parts
[0396] The above materials were mixed and heated to 100°C, dispersed using a homogenizer (ULTRA-TURRAX T50 manufactured by IKA), and then dispersed using a pressure-dispensing Gaulin homogenizer to obtain a release agent particle dispersion in which release agent particles having a volume average particle size of 200 nm were dispersed. Deionized water was added to the release agent particle dispersion to adjust the solid content to 20%, thereby obtaining a release agent particle dispersion (W1).
[0397] [Preparation of Colorant Particle Dispersion Liquid (Y1)]
[0398] Yellow pigment (CI Pigment Yellow 180): 50 parts
[0399] Anionic surfactant (manufactured by DKS Co. Ltd., NEOGEN RK): 5 parts
[0400] Deionized water: 195 parts
[0401] The above materials were mixed and dispersed for 60 minutes using a high-pressure impact disperser (ULTIMAIZER HJP30006, SUGINO MACHINE LIMITED CO., LTD.) to obtain a colorant particle dispersion (K1) having a solid content of 20%.
[0402] [Preparation of Yellow Toner Particles (Y1)]
[0403] Deionized water: 200 parts
[0404] Amorphous polyester resin dispersion (A1): 150 parts
[0405] Crystalline polyester resin dispersion (C1): 10 parts
[0406] Release agent particle dispersion (W1): 10 parts
[0407] Colorant particle dispersion (Y1): 15 parts
[0408] Anionic surfactant (TaycaPower): 2.8 parts
[0409] The above materials were placed in a round stainless steel flask, 0.1N nitric acid was added, and the pH was adjusted to 3.5. Then, an aqueous solution of polyaluminum chloride (manufactured by Oji Paper Co., Ltd., 30% powder product) was added, which was prepared by dissolving 2 parts of polyaluminum chloride in 30 parts of deionized water. After dispersion at 30°C using a homogenizer (ULTRA-TURRAX T50 manufactured by IKA), the mixture was heated to 45°C in a heating oil bath and maintained until the volume average particle size reached 4.9 μm. Next, 60 parts of amorphous polyester resin dispersion (A1) were added and maintained for 30 minutes. Next, when the volume average particle size reached 5.2 μm, 60 parts of amorphous polyester resin dispersion (A1) were further added and maintained for 30 minutes. Next, 20 parts of a 10% aqueous solution of NTA (nitrilotriacetic acid) metal salt (CHELEST 70, manufactured by CHELEST CORPORATION) were added, and a 1N aqueous solution of sodium hydroxide was added to adjust the pH to 9.0. Next, 1 part of an anionic surfactant (Tayca Power) was added, and the mixture was heated to 85° C. and maintained for 5 hours while being continuously stirred. Next, the mixture was cooled to 20° C. at a rate of 20° C. / min. Next, the mixture was filtered, washed thoroughly with deionized water, and dried to obtain yellow toner particles (Y1) having a volume average particle size of 5.7 μm and an average circularity of 0.971.
[0410] Next, silicon dioxide (SiO2) particles with an average primary particle size of 40 nm, which have been surface-hydrophobized using hexamethyldisilazane (hereinafter sometimes referred to as "HMDS"), and titanate compound particles with an average primary particle size of 20 nm, which are the reaction product of titanic acid and isobutyltrimethoxysilane, are added to the yellow toner particles (Y1) so that the coverage rate relative to the surface of the toner particles becomes 40%, and the mixture is mixed using a Henschel mixer to produce a yellow toner (Y1).
[0411] [Preparation of mixed solution 1]
[0412] Lacquer (a solution prepared by mixing 20 parts of polycyclohexyl methacrylate (weight average molecular weight: 68,000, glass transition temperature Tg: 110°C) with 80 parts of toluene): 100 parts
[0413] Carbon black (average particle size 0.2 μm): 0.2 parts
[0414] The above materials were put into a sand mill and dispersed for 30 minutes to obtain a mixed solution 1.
[0415] (Example 1)
[0416] Ferrite core (volume average particle size 35 μm): 100 parts
[0417] Mixed liquid 1: 3.0 parts per 100 parts of the resin solid content of the ferrite core
[0418] The above components were put into a batch stirring type vacuum mixer (50L kneader manufactured by INOUEMFG., INC., stirring blade diameter D = 0.25m, gap between the outer periphery of the blade and the inner wall of the shell / D = 3.5%) with the jacket temperature heated to 90°C, and stirred and mixed at 60rpm while preheating (heating) to 70°C. Next, the internal pressure of the mixer was reduced to 5kPa-abs, and it was continued until the load power value of the stirring blade before the solvent drying increased as the drying progressed, and the drying was completed and the load power value dropped to less than 1.3 times the value before drying, and a resin coating layer was formed on the surface of the magnetic particles to obtain resin-coated magnetic particles. At this time, the temperature of the obtained resin-coated magnetic particles rose to 98°C. Next, while maintaining the resin-coated magnetic particles at 100°C, the resin-coated magnetic particles were decomposed and crushed in the mixer for 30 minutes. In addition, the decomposition and crushing conditions of the resin-coated magnetic particles are summarized in Table 1.
[0419] Next, the stirring of the mixer was stopped, and the decomposed and crushed resin-coated magnetic particles were directly added from the mixer to a fluidized bed device (manufactured by OKAWARA MFG.CO., LTD., slit flow). In the fluidized bed device, the fluidizing gas heated to 100°C was discharged at an empty tower velocity of 20 mm / s (twice the value of the minimum fluidization velocity Umf), so that the resin-coated magnetic particles flowed for 60 minutes while maintaining 100°C. Next, the fluidizing gas at 20°C was discharged at an empty tower velocity of 100 mm / s (10 times the value of the minimum fluidization velocity Umf), and the resin-coated magnetic particles were cooled for 80 minutes, so that the temperature of the resin-coated magnetic particles was reduced to 70°C. Then, the resin-coated magnetic particles were taken out from the fluidized bed device, and the carrier 1 was prepared by sieving with a mesh opening of 75 μm. In addition, the flow conditions and cooling conditions in the fluidized bed device are summarized in Table 1.
[0420]
[0421] (Example 2 to Example 15)
[0422] As shown in Table 1 above, carriers 2 to 15 were prepared in the same manner as in Example 1 except that one or more of the decomposition and crushing conditions of the resin-coated magnetic particles in step A, the flow conditions of the resin-coated magnetic particles in step B, and the cooling conditions in step C were changed.
[0423] (Example 16)
[0424] [Preparation of mixed solution 2]
[0425] Lacquer (a solution prepared by mixing 20 parts of polycyclohexyl methacrylate (weight average molecular weight: 50,000, glass transition temperature Tg: 100°C) with 80 parts of toluene): 100 parts
[0426] Carbon black (average particle size 0.2 μm): 0.2 parts
[0427] The above materials were put into a sand mill and dispersed for 30 minutes to obtain a mixed solution 2.
[0428] A carrier 16 was prepared in the same manner as in Example 1 except that the mixed solution 2 was used and the conditions shown in Table 1 were used.
[0429] (Comparative Example 1)
[0430] Ferrite core (volume average particle size 35 μm): 100 parts
[0431] Mixed liquid 1: 3.0 parts per 100 parts of the resin solid content of the ferrite core
[0432] The above components were placed in a batch stirring type vacuum mixer (50L kneader manufactured by INOUEMFG., INC., stirring blade diameter D = 0.25m, gap between the outer periphery of the blade and the inner wall of the shell / D = 3.5%) with the jacket temperature heated to 90°C, and stirred and mixed at 60rpm while preheating (heating) to 70°C. Next, the internal pressure of the mixer was reduced to 5kPa-abs, and this was continued until the load power value of the stirring blade before the solvent drying increased as the drying progressed, and the drying was completed and the load power value decreased to less than 1.3 times the value before drying, and a resin coating layer was formed on the surface of the magnetic particles to obtain resin-coated magnetic particles. At this time, the temperature of the obtained resin-coated magnetic particles rose to 98°C. Next, the jacket temperature of the mixer was cooled to 20°C, and the temperature of the resin-coated magnetic particles was cooled to 70°C while the resin-coated magnetic particles were decomposed and crushed over 90 minutes. Then, the resin-coated magnetic particles were taken out from the mixer and sieved with a mesh opening of 75 μm to prepare a carrier C1.
[0433] In addition, Table 1 shows the decomposition and pulverization conditions in the mixer in summary.
[0434] (Comparative Example 2)
[0435] In step B, the resin-coated magnetic particles were allowed to flow for 60 minutes while maintaining the temperature at 85°C. In step C, the resin-coated magnetic particles were cooled for 60 minutes to reduce the temperature of the resin-coated magnetic particles to 60°C. Except for this, the carrier C2 was prepared in the same manner as Example 1.
[0436] (Comparative Example 3)
[0437] In step B, the resin-coated magnetic particles were allowed to flow for 60 minutes while maintaining a temperature of 165°C. In step C, the resin-coated magnetic particles were cooled for 120 minutes to reduce the temperature of the resin-coated magnetic particles to 70°C. Except for this, the carrier C3 was prepared in the same manner as Example 1.
[0438] <Production of developer>
[0439] Any one of Carriers 1 to 16 and C1 to C3 and yellow toner (Y1) were put into a V mixer at a mixing ratio of Carrier:Toner=100:10 (mass ratio) and stirred for 20 minutes to obtain Developers 1 to 16 and C1 to C3, respectively.
[0440] <Various measurements and evaluations>
[0441] -Determination of the coating ratio of the resin coating layer in the carrier-
[0442] The coverage rate of the resin coating layer on the carrier surface was determined by X-ray photoelectron spectroscopy (XPS) in the following manner.
[0443] A carrier as a subject and magnetic particles after the resin coating layer is removed from the carrier as a subject are prepared. As a method for removing the resin coating layer from the carrier, a method of removing the resin coating layer by dissolving the resin component with toluene is used. The carrier and the magnetic particles after the resin coating layer is removed are respectively used as measurement samples, and Fe, C, and O (atomic %) are quantified by XPS, and the exposure ratio (%) of the magnetic particles is calculated by (Fe of the carrier) ÷ (Fe of the magnetic particles) × 100, and (100-exposure ratio of the magnetic particles) is set as the coverage ratio (%) of the resin coating layer.
[0444] -Determination of the amount of free resin in the carrier-
[0445] A certain amount of carrier was weighed and dispersed in water, and the dispersion was filtered while the carrier was fixed with a magnet. The filter paper was dried, and the amount of free resin was calculated based on the difference in mass before and after the filter paper and the amount of carrier weighed.
[0446] -Determination of the ratio of aggregates in the carrier after 75 μm sieving-
[0447] The carriers were sieved using a sieve with a pore size of 75 μm. The sieved carriers were spread out in a manner that minimized overlap, and a 350x scanning electron microscope (SEM) photograph was taken. The ratio of the number of carriers that were not decomposed and crushed to primary particles was measured relative to the number of carriers in one field of view.
[0448] -Evaluation of color fading suppression-
[0449] Evaluation of dullness of color was performed as follows.
[0450] Using the 700 Digital Color Press (manufactured by FUJIFILM Business Innovation Corp.) filled with the obtained developer, a 5 cm × 5 cm solid image logo (Sample 1) was printed, and after printing 100,000 images with 5% area coverage, a 5 cm × 5 cm solid image logo (Sample 2) was printed again. Then, the color gamut (L * 、a * 、b * ). In addition, the color gamut was measured by an image densitometer X-RITE938 (manufactured by X-RITE Corporation).
[0451] Based on the difference between the color gamut of Sample 2 and the color gamut of Sample 1, ΔE was calculated using the following formula and used as an evaluation index for color dullness.
[0452] ΔE=〔(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 〕 1 / 2
[0453] Here, ΔL * =(L of sample 2 * - L of sample 1 * ), Δa * =(a of sample 2 * -a of sample 1 * ), Δb * =(b of sample 2 * - Sample 1 b * )
[0454] The evaluation criteria are as follows.
[0455] -Evaluation Criteria-
[0456] G1: ΔE≤1.0
[0457] G2: 1.0<ΔE≤2.0
[0458] G3: 2.0<ΔE≤3.0
[0459] G4: 3.0<ΔE≤5.0
[0460] G5: 5.0<ΔE≤7.0
[0461] G6: 7.0<ΔE≤10.0
[0462] G7: 10.0<ΔE
[0463] Table 2 shows the results of the measurements and evaluations in summary.
[0464] [Table 2]
[0465]
[0466] The above results show that the image obtained in the present example is superior in color fading suppression property compared to the comparative example.
[0467] Hereinafter, aspects of the present invention will be supplementally described.
[0468] (1) A method for producing a carrier for developing an electrostatic latent image, comprising:
[0469] Step A, mixing a mixed solution containing a resin having a glass transition temperature Tg and a solvent with magnetic particles in a mixer, and heating the mixture to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then maintaining the resin-coated magnetic particles at a temperature Tg. A Decomposition and crushing in a state;
[0470] Step B, in a fluidized bed apparatus, maintaining the resin-coated magnetic particles after step A at a temperature T B flows in a state of
[0471] Step C, cooling the resin-coated magnetic particles after step B,
[0472] The temperature T A And the temperature T B The glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower are satisfied independently.
[0473] (2) The method for producing a carrier for electrostatic latent image development according to (1), wherein:
[0474] In the step A, the resin-coated magnetic particles are stirred at a temperature T using a mixer having a stirring blade. A The stirring conditions in the mixer when decomposing and pulverizing are performed in a state satisfy the conditions of the following formula 1 and the following formula 2.
[0475] 0.2≤the peripheral speed of the stirring blade πDN (m / s)≤2.0 Formula 1
[0476] 5×10 2 ≤Stirring workload (circumferential speed πDN×stirring time T)≤1.5×10 3 Formula 2
[0477] In Formula 1 and Formula 2, D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
[0478] (3) The method for producing a carrier for electrostatic latent image development according to (2), wherein:
[0479] The conditions of the above formula 2 are the conditions of the following formula 2'.
[0480] 7×10 2 ≤Stirring workload (circumferential speed πDN×stirring time T)≤1×10 3 Formula 2'
[0481] In Formula 2', D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
[0482] (4) The method for producing a carrier for electrostatic latent image development according to any one of (1) to (3), wherein:
[0483] In the step B, the resin-coated magnetic particles after the step A are maintained at a temperature T B In the step C, the temperature T of the resin-coated magnetic particles is lowered to C Cool to the glass transition temperature Tg-40°C or below.
[0484] (5) The method for producing a carrier for electrostatic latent image development according to any one of (1) to (4), wherein:
[0485] In the step B, the resin-coated magnetic particles after the step A are maintained at a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H (m / s) satisfies 1 to 5 times the minimum fluidization velocity Umf.
[0486] (6) The method for producing a carrier for electrostatic latent image development according to (5), wherein:
[0487] The superficial velocity V of the fluidizing gas in the fluidized bed device H Satisfies a minimum fluidization velocity of at least 2 times and at most 3 times the minimum fluidization velocity Umf.
[0488] (7) A method for producing an electrostatic latent image developer, comprising the method for producing a carrier for electrostatic latent image development according to any one of (1) to (6).
[0489] According to the invention described in (1), there is provided a method for producing a carrier for electrostatic latent image development, wherein the method comprises steps A, B and C, and the temperature TA is lower than the glass transition temperature Tg-20°C and step B is not performed, or the temperature T B In the step A, a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer, and heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are maintained at a temperature Tg. A In step B, the resin-coated magnetic particles after step A are maintained at a temperature T in a fluidized bed apparatus. B In step C, the resin-coated magnetic particles after step B are cooled.
[0490] According to the invention described in (2), there is provided a method of maintaining the temperature T of the resin-coated magnetic particles in step A. A A method for producing a carrier for electrostatic latent image development having better color fading suppression of the obtained image when the stirring conditions in the mixer during decomposition and pulverization do not satisfy the conditions of the above-mentioned formula 2.
[0491] According to the invention described in (3), there is provided a method of maintaining the temperature T of the resin-coated magnetic particles in step A. AA method for producing a carrier for electrostatic latent image development having better color fading suppression of the obtained image when the stirring conditions in the mixer during decomposition and pulverization satisfy the conditions of the above formula 2 but do not satisfy the conditions of the above formula 2'.
[0492] According to the invention described in (4), there is provided a method of maintaining the resin-coated magnetic particles at a temperature T B After the resin-coated magnetic particles flow for less than 30 minutes, the temperature T C When the resin-coated magnetic particles after step A are cooled to a glass transition temperature Tg-40°C or lower, or when the resin-coated magnetic particles after step A are maintained at a temperature T B After the resin-coated magnetic particles flow for more than 30 minutes, the temperature T C A method for producing a carrier for developing an electrostatic latent image, wherein the carrier is cooled to a temperature lower than the glass transition temperature Tg-40° C., and the obtained image has a more excellent color fading suppression property.
[0493] According to the invention described in (5), there is provided a method of maintaining the resin-coated magnetic particles after step A at a temperature T in step B. B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H A method for producing a carrier for developing an electrostatic latent image in which the color fading of the obtained image is more excellent when the minimum fluidization velocity (m / s) exceeds 5 times the minimum fluidization velocity Umf.
[0494] According to the invention described in (6), there is provided a method of maintaining the resin-coated magnetic particles after step A at a temperature T in step B. B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H A method for producing a carrier for developing an electrostatic latent image in which the color fading of the obtained image is more excellent when the minimum fluidization velocity Umf (m / s) is more than 3 times and less than 5 times.
[0495] According to the invention described in (7), there is provided a method for producing an electrostatic latent image developer, which comprises steps A, B and C, and wherein the temperature T A When the temperature is lower than the glass transition temperature Tg-20°C and step B is not performed, or the temperature T BThe method for producing a carrier for electrostatic latent image development having a glass transition temperature lower than the glass transition temperature Tg-20°C or higher than the glass transition temperature Tg+50°C has excellent color fading suppression of the obtained image, wherein in the step A, a mixed solution containing a resin having a glass transition temperature Tg and a solvent and magnetic particles are mixed in a mixer and heated to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then the resin-coated magnetic particles are heated to a temperature of Tg. A In step B, the resin-coated magnetic particles after step A are maintained at a temperature T in a fluidized bed apparatus. B In step C, the resin-coated magnetic particles after step B are cooled.
[0496] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the art can understand the present invention through various variations optimized for specific uses assumed to be various embodiments. The scope of the present invention is defined by the above claims and their equivalents.
Claims
1. A method for producing a carrier for electrostatic latent image development, comprising: Step A, mixing a mixed solution containing a resin having a glass transition temperature Tg and a solvent with magnetic particles in a mixer, and heating the mixture to evaporate the solvent and form a resin coating layer on the surface of the magnetic particles to obtain resin-coated magnetic particles, and then maintaining the resin-coated magnetic particles at a temperature Tg. A Decomposition and crushing in a state; Step B, in a fluidized bed apparatus, maintaining the resin-coated magnetic particles after step A at a temperature T B flows in a state of Step C, cooling the resin-coated magnetic particles after step B, The temperature T A And the temperature T B The glass transition temperature Tg-20°C or higher and the glass transition temperature Tg+50°C or lower are satisfied independently.
2. The method for producing a carrier for developing an electrostatic latent image according to claim 1, wherein: In the step A, the resin-coated magnetic particles are stirred at a temperature T A The stirring conditions in the mixer when the decomposition and crushing are performed in the state satisfy the conditions of the following formula 1 and the following formula 2, 0.2≤the peripheral speed of the stirring blade πDN (m / s)≤2.0 Formula 1 5×10 2 ≤Stirring workload (circumferential speed πDN×stirring time T)≤1.5×10 3 Formula 2 In Formula 1 and Formula 2, D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
3. The method for producing a carrier for developing an electrostatic latent image according to claim 2, wherein: The condition of Formula 2 is the condition of the following Formula 2', 7×10 2 ≤Stirring workload (circumferential speed πDN×stirring time T)≤1×10 3 Formula 2' In Formula 2', D represents the diameter of the stirring blade (m), N represents the rotation speed of the stirring blade (rps), and T represents the time (s) from the moment when the load power value of the stirring blade before the solvent is dried increases as the drying proceeds, to the moment when the drying is completed and the load power value drops to less than 1.3 times the value before drying, to the moment when the stirring in the mixer is completed.
4. The method for producing a carrier for developing an electrostatic latent image according to any one of claims 1 to 3, wherein: In the step B, the resin-coated magnetic particles after the step A are maintained at a temperature T B In the step C, the temperature T of the resin-coated magnetic particles is lowered to C Cool to the glass transition temperature Tg-40°C or below.
5. The method for producing a carrier for developing an electrostatic latent image according to any one of claims 1 to 4, wherein: In the step B, the resin-coated magnetic particles after the step A are maintained at a temperature T B The superficial velocity V of the fluidizing gas in the fluidized bed device when flowing in the state of H (m / s) satisfies 1 to 5 times the minimum fluidization velocity Umf.
6. The method for producing a carrier for developing an electrostatic latent image according to claim 5, wherein: The superficial velocity V of the fluidizing gas in the fluidized bed device H Satisfies a minimum fluidization velocity of at least 2 times and at most 3 times the minimum fluidization velocity Umf. 7 . A method for producing an electrostatic latent image developer, comprising the method for producing a carrier for developing an electrostatic latent image according to claim 1 .
Citation Information
Patent Citations
Production of electrophotographic carrier
JP1996234499A
Manufacturing method of carrier for electrostatic charge image development, manufacturing method of electrostatic charge image developer, image formation method and carrier for electrostatic charge image development
JP2022147738A